Genetic ancestry proportion influences risk of adverse events from tuberculosis treatment in Brazil - Jacqueline A. Piekos; Gustavo Amorim; Felipe Ridolfi; Marcelo Cordeiro-Santos; Afrânio L. Kritski; Marina C. Figueiredo; Bruno B. Andrade; Adalberto R. Santos; David W. Haas; Timothy R. Sterling; Valeria C. Rolla; Digna R. Velez Edwards; et al. (Human Genetics, 2026)
Tuberculosis (TB) treatment is highly effective, but response to therapy varies by geography and population subgroups. We assessed differences in TB treatment response in a representative and heterogeneous Brazilian population. We estimated genetic ancestry according to major genetic ancestry groups (African, European, and Amerindian) in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil cohort using ADMIXTURE software. RePORT-Brazil is an observational prospective cohort study of individuals with newly-diagnosed, culture-confirmed, pulmonary TB. Outcomes attributed to TB treatment included Grade 2 or higher adverse drug reaction (ADR), Grade 3 or higher ADR, hepatic ADR, and failure/recurrence. Genetic ancestry proportions were evaluated as predictors in univariate and multivariable logistic regression models for each outcome, and in stratified models for each genetic ancestry group. There were 930 pulmonary TB patients included in this study. In multivariable models we observed a decreased risk of Grade 2 + ADR when African ancestry proportion increased by 10% (Odds Ratio [OR] 0.41, 95% Confidence Interval [CI] 0.20–0.85) and an increased risk for Grade 2 + ADR with increasing European genetic ancestry (OR 2.33, 95% CI 1.14–4.76). In secondary analyses evaluating the interaction of HIV and genetic ancestry, we observed a statistically significant interaction between HIV and African genetic ancestry, but significantly decreased risk for Grade 2 + ADR with increasing African ancestry proportion. There were no associations with Amerindian genetic ancestry or for other treatment outcomes. In this Brazilian TB cohort, increased toxicity risk was associated with decreased African and increased European ancestry proportion.

Climate sensitivity and glacial inception in the European Alps across marine isotope stage 11 and 10 - Alexandre Honiat; Jonathan L. Baker; Gina E. Moseley; Martin Trüssel; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

Reconstructing prehistoric land cover and landuse in complex ‘blue-green’ landscapes - Kimberley L. Davies; M. Jane Bunting; Willem Koster; Nicki J. Whitehouse; Michelle Farrell; Henry Chapman; Jason R. Kirby; J. Edward Schofield; Phil Barratt; Benjamin Gearey; Nika Shilobod (Vegetation History and Archaeobotany, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Nitrogen partitioning between plant species and soil microbes in alpine heath - Ellen L. Fry; Jonathan R. De Long; Edward Ayres; René van der Wal; Richard D. Bardgett (Soil Biology and Biochemistry, 2026)

Development of inflation ridges over Lava tubes - Edward A. Williams; Laurent G.J. Montési; Patrick L. Whelley; Ernest R. Bell (Journal of Volcanology and Geothermal Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Using a Combination Amino Acid, Carbohydrate, and Micronutrient Beverage for Preoperative Nutrition Allows Safe Gastric Emptying for Anesthesia Provision in a Prospective, Single-Group Intervention - Jennifer A. Bowden; Sarah Heath; Gregory L. Snow; Anton E. Bowden; John R. Edwards (Journal of the Academy of Nutrition and Dietetics, 2026)

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Acute nutritional ketosis during early recovery from aerobic exercise does not affect skeletal muscle transcriptomic response in humans - Erick Mosquera-Lopez; Julien Louis; Jason P. Edwards; Jamie Pugh; Mark R. Viggars; Daniel J. Owens; Jose L. Areta (European Journal of Applied Physiology, 2026)
Purpose Nutritional ketosis is purported to enhance skeletal muscle recovery and adaptation to exercise, yet precise adaptive mechanisms are unknown. We investigated the post-exercise molecular response to ketone monoesters (KME) in skeletal muscle by characterising the early transcriptomic response. Methods Following a randomised, double-blind, crossover design, recreationally active men (n = 9, age: 26 ± 5 (means ± SD) y; V̇O 2max : 47 ± 4 mL·kg −1 ·min −1 ) completed two experimental trials where they ingested either 1.25 g·kg −1 of KME or a taste-matched placebo (PLA) drink during exercise (90-min cycling at 60% of V̇O 2max ) and 3-h recovery. Blood samples were taken throughout for hormone and metabolite analyses, and muscle biopsies were taken at baseline and 3 h post-exercise for glycogen and genome-wide gene expression analyses. Results Recovery ßHB concentrations were higher in KME (4.1 ± 0.7 mM) vs PLA (0.1 ± 0.0 mM, P < 0.001). Erythropoietin (EPO) showed a main effect of time ( P = 0.044), but no condition effect ( P = 0.087) or interaction ( P = 0.318). Skeletal muscle glycogen decreased post-exercise (−57%, P < 0.001) as expected, but showed no condition effect ( P = 0.889) or interaction ( P = 0.907). We measured the expression of 16,898 genes, and despite a clear time effect on the skeletal muscle transcriptome (1561 differentially expressed genes post vs pre-exercise; q < 0.05 fold change > ± 1.5), there was no effect of condition. Conclusions KME did not demonstrate an effect on EPO concentration, muscle glycogen or transcriptome, suggesting DNA translation is likely not a process directly regulated by acute ketonaemia that increases early post-exercise.

Record Rainfall from the Enhanced Southwest Monsoon in Metro Manila, Philippines: A Comparative Study of Recent Events - Lyndon Mark Payanay Olaguera; Alwin Andriel L. Bathan; Edward Kyle Badua; Erica N. Bañares; Clint Eldrick R. Petilla; John A. Manalo; Faye Abigail T. Cruz; Jose Ramon T. Villarin (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Meal Preparation Strategies and Lack of Food Security Among Unaccompanied Latino Migrant Farmworker Youth in Georgia and Florida: A Mixed-Methods Approach - Fiorella L. Carlos Chavez; Kaleea R. Lewis; Bethany A. Moore; Tracy Tang; Edward D. Vargas; Joan M. Hermsen; Rebecca E. Lee; Youngbin Lee; Irma A. Arteaga; Khushi Bypan; J. Sanford Rikoon; Thomas A. Arcury (Journal of Agromedicine, 2026)

Validating the children's eating behaviour questionnaire in a UK sample: A suitable tool for mothers and fathers - Mar Lozano-Casanova; Silvia Escribano; Abigail Pickard; Katie L. Edwards; Alice R. Kininmonth; Miguel Richart-Martinez; Isabel Sospedra; Claire Farrow; Jacqueline Blissett (Appetite, 2026)

Parent reports of eating behaviour and feeding practices: effects of parent and child sex - Mar Lozano-Casanova; Katie L. Edwards; Abigail Pickard; Emma Haycraft; Alice R. Kininmonth; Miguel Richart-Martinez; Isabel Sospedra; Claire Farrow; Jackie Blissett (Appetite, 2026)

Passive Acoustic Monitoring Reveals Temporal and Environmental Drivers of the Cetacean Community in the Southern Great Barrier Reef - Isabel A. R. Taylor; Sophie Beutel; Christine L. Dudgeon; Asia O. Armstrong; Kathy A. Townsend; Romney Edwards‐Francis; Dominique A. Potvin (Marine Mammal Science, 2026)
Monitoring cetaceans in Australia's Great Barrier Reef (GBR) is essential for understanding their ecological roles and informing conservation, yet traditional visual surveys are limited by logistical constraints. Passive acoustic monitoring (PAM) offers a complementary solution, particularly in acoustically complex coral‐reef habitats of the southern GBR. Over 2 years, we deployed an autonomous recorder at Lady Elliot Island to document cetacean presence and assess environmental associations. We detected vocalizations from humpback whales ( Megaptera novaeangliae ), dwarf minke whales ( Balaenoptera acutorostrata subsp.), and delphinids, likely spinner ( Stenella longirostris ) and/or bottlenose dolphins ( Tursiops spp.). Humpback whale song dominated recordings from June through October, while dwarf minke whale “Star‐Wars” calls occurred from May to August, marking the first acoustic evidence of this subspecies within the southern GBR. Dwarf minke whale detections correlated positively with chlorophyll‐ a concentration, whereas humpback whale detections were negatively associated with wind speed. Rorqual vocalizations declined during periods of elevated anthropogenic noise, while odontocete detections remained unaffected. These results highlight PAM's effectiveness for detecting cetaceans within complex reef soundscapes and suggest acoustic niche partitioning among taxa. These critical baseline data inform management strategies for understudied GBR cetacean populations and establish a robust framework for future long‐term monitoring efforts and effective conservation actions.

The coupling between monsoon rainfall and Sea Surface Temperature in the subtropical South Atlantic during the Last Glacial Period - Lucas C. Vasconcelos; Francisco W. Cruz; Juan Pablo Bernal; Marília C. Campos; Patrícia Piacsek; José L. Campos; Haiwei Zhang; Nicolás Stríkis; Mathias Vuille; Giselle Utida; Christian Millo; R. Lawrence Edward; et al. (Global and Planetary Change, 2025)

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Hidden Nutrient Gaps: The Association Between Healthy Eating index-2020 Scores and Micronutrient Gaps - C. Edwards; J. Townsend; P. Sapp; T. Kirby; L. Nyman; R. Esposito (Journal of the Academy of Nutrition and Dietetics, 2025)

AG1® Supplementation Improves Gut Microbiome Composition and Relative Abundance of Growth/Nutrient Metabolism Gene Pathways in Adults with Occasional Gastrointestinal Issues - T. Kirby; J. Townsend; P. Sapp; C. Edwards; J. Wright; R. Lamendella; L. Nyman; R. Esposito (Journal of the Academy of Nutrition and Dietetics, 2025)

Sugarcane genotype by environment interaction (G × E) in clonal trials in the U.S. Texas Rio Grande Valley - James R. Todd; Orlando Coto Arbelo; Anna L. Hale; Yong-Bao Pan; Edwis O. Dufrene; David Verdun; Aliya Momotaz; Collins A. Kimbeng; Herman L. Waguespack; Andrew W. Scott; Edward Hernandez; Matthew Klostermann (Euphytica, 2025)

Patterns of coral spawning in the Palm Islands, Great Barrier Reef - Hanaka Mera; Alasdair J. Edwards; James R. Guest; Liam Lachs; Kate M. Quigley; Bette L. Willis; Andrew H. Baird (Coral Reefs, 2025)
Scleractinian reproductive biology has been a focus of research since the discovery of multi-species synchronous spawning in the early 1980s; however, predicting when colonies will spawn on the Great Barrier Reef remains problematic. Here, we combine over 30 years of direct coral spawning observations that include colonies from 128 species from 44 genera in 10 families with 20 years of data on the stage of gamete maturity in colonies of Acropora (hereafter, colony reproductive condition) from the Palm Island group on the Great Barrier Reef to explore patterns within and among species. We find the lunar month counted from the southern hemisphere winter solstice better predicts the first month of spawning in the Palm Islands than the Gregorian month: spawning was never observed before the 5th lunar month. Direct observations suggest that most coral spawning in the Palm Islands occurs in the 5th and 6th lunar months over a 12-day interval starting one day before the full moon, between 30 min before and 5 h after sunset. Split spawning was also a frequent occurrence in Acropora populations. Some Acropora spp. had colonies that spawned in four or five different lunar months, a pattern that might be affected by taxonomic uncertainty. The range in spawning start times was considerably greater among colonies maintained in the laboratory vs those in the field, suggesting that spawning times are affected by handling. This work highlights the importance of a systematic approach to documenting spawning times to improve our understanding of spawning synchrony and seasonality.

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Microscale analysis of the fish Knightia eocaena taphonomy: Implication of a preserved microbial community - Garrett A. Rogers; Dakota R. Pittinger; Edward L. Simpson; Kurt Friehauf (Palaeobiodiversity and Palaeoenvironments, 2025)
Microbial communities are important components controlling the fidelity of fossil fish preservation. The Eocene Green River Formation lagerstätten, exceptionally preserved fossil deposits, provides an opportunity to examine the role of microbial communities and their metabolic byproducts, such as chemical precipitated in this spectacularly preserved fish deposit, famous throughout the world. Field emission scanning electron microscope (FESEM) and energy dispersive spectroscopy system (EDS) examination of a well-preserved Knightia eocaena from the Eocene Green River Formation documents the presence of bacteriomorphs. Bacteriomorphs in a sample from the Fossil Butte Member of the Green River Formation consists of spherical structures, coccoid-type bacteria, fibres from two-sized populations of filamentous bacteria, probable filamentous cyanobacteria, capsule-shaped, and bacilliform bacteria, all associated with framboidal iron hydroxide. Bacteriomorphs consist of external molds composed of nanometer-scale calcium carbonate spheres. Fe-oxide framboids have an amorphous exterior and a sieve-like internal structure. The sieve-like structure consists of nanometer-scale pores, probable sites of bacterial cells with walls composed of 100-nanometer-scale spheres. Fe-oxides are consistent with bacterially mediated precipitation of pyrite followed by an oxidation event. Preserved bacteriomorphs are consistent with degradation of soft tissue, limiting the preservation of soft tissue and leaving bone and scales with no appreciable soft tissue. The microfossils are restricted to the skeleton and are not found in the surrounding rock matrix, suggesting larger microbial mats may not have been present and possibly did not have a significant impact on the preservation of this specimen.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Biogeochemical controls on iron speciation and cycling across upland to shoreline gradients in freshwater and estuarine coastal soils (Lake Erie and Chesapeake Bay, United States) - Lucie Stetten; Maxim I. Boyanov; Edward J. O'Loughlin; Shan Pushpajom Thomas; Kathleen R. Beilsmith; Roberta B. Peixoto; Fausto Machado-Silva; Donnie J. Day; Stephanie J. Wilson; Timothy W. Vugteveen; Allison N. Myers-Pigg; Opal Otenburg; et al. (Science of The Total Environment, 2025)

Grazing deterrents improve survival of outplanted juvenile corals - Eveline van der Steeg; Adriana Humanes; John C. Bythell; Jamie R. Craggs; Alasdair J. Edwards; Yimnang Golbuu; Liam Lachs; Margaret W. Miller; Janna L. Randle; James R. Guest (Coral Reefs, 2025)
High mortality of juvenile corals hinder both the natural recovery of populations and the successful implementation of restoration efforts. Grazing is a significant cause of juvenile coral mortality, and grazer exclusion devices have been shown to increase juvenile coral survivorship. However, most experiments have used cages that typically alter water flow and light conditions, making it difficult to separate abiotic effects from those of grazing. Here, we test whether grazing deterrents can increase the survival and growth of six-month-old Acropora digitifera juveniles outplanted to a shallow reef crest, using arrangements of two or four long or short masonry nails designed to physically exclude larger grazers (e.g., parrotfish) while minimising abiotic changes. By the end of our study, colonies with deterrents had significantly larger planar area (almost tenfold for the most effective treatment), more branches, greater height, and higher survival than those without deterrents. A critical period in this study was the first week after outplanting when colonies with deterrents had significantly less tissue area loss from grazing than those without. Lower area loss in the first week was associated with significantly higher survival over the following 14 months, with an almost threefold improvement for the most effective treatment. For heavily grazed systems, our study highlights the importance of incorporating grazing deterrents into outplant devices to counteract the negative impact of large grazers on newly outplanted juvenile corals and boost restoration success.

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Production and immunogenicity of a plant-produced beak and feather disease virus vaccine in Japanese quails - Goodman Mulondo; Mélie L. R. Buyse; Kimberley Labuschagne; David Jarvis; Albertha van Zyl; Edward P. Rybicki; Inga I. Hitzeroth; Sandiswa Mbewana (Archives of Virology, 2025)
Beak and feather disease virus (BFDV), a single-stranded DNA virus, infects endangered psittacine species, including the South African Cape parrot. The disease is highly contagious and can be transmitted through contact with contaminated faeces, crop secretions, and feather and skin dander. To date, there is no vaccine or cure available for BFDV. The production of an effective vaccine depends on having a production platform and methods that are both easy to use and capable of yielding a significant amount of protein that will induce a sufficient immune response. Therefore, the aim of this study was to produce a plant-based BFDV vaccine candidate and to evaluate its ability to elicit an immune response in birds. Recombinant BFDV capsid protein (CP) was transiently expressed in Nicotiana benthamiana and purified using density gradient ultracentrifugation. Japanese quails were immunized with purified BFDV CP. Yolk-derived IgY was purified by water dilution and salt precipitation, and its specificity was verified by western blot analysis. The expression levels of the coat protein increased from non-detectable to an average accumulation of 1.58 mg/kg of fresh plant tissue biomass, and antibodies against BFDV CP were detected in both the blood and eggs of immunized quails, indicating that vaccination with BFDV CP successfully elicited a humoral immune response. This study demonstrates that heterologous expression in plants is a viable method for producing BFDV CP. To the best of our knowledge, this is the first study to show the antibody response to a plant-produced BFDV antigen in a quail model. Given that the presence of anti-CP antibodies in infected birds is associated with immunity, this system can potentially be used to produce a vaccine against BFDV.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Corrigendum to “Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery” [Mar. Policy 155 (2023) 105739] - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Influence of wind on movement behaviour in Arctic grizzly bears - Julia L. Self; Ron R. Togunov; Mark A. Edwards; Andrew E. Derocher (Behavioural Processes, 2025)

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Investigating stocking density, culture duration, and the combination ratio of artificial feed and fresh feed for mangrove crab Scylla serrata megalopae reared in pond-based net cages - Pedrita A. Caballero; Veronica R. Alava; Kyle Dymer L. Regatalio; Rheniel Dayrit; Joseph P. Faisan; Roger Edward P. Mamauag; Mercedes M. Pates; Gaudioso S. Pates (Aquaculture International, 2025)

Warming Disrupts Plant–Fungal Endophyte Symbiosis More Severely in Leaves Than Roots - Joseph D. Edwards; Melanie R. Kazenel; Yiqi Luo; Joshua S. Lynn; Rebecca L. McCulley; Lara Souza; Carolyn Young; Jennifer A. Rudgers; Stephanie N. Kivlin (Global Change Biology, 2025)
Disruptions to functionally important symbionts with global change will negatively impact plant fitness, with broader consequences for species' abundances, distribution, and community composition. Fungal endophytes that live inside plant leaves and roots could potentially mitigate plant heat stress from global warming. Conversely, disruptions of these symbioses could exacerbate the negative impacts of warming. To better understand the consistency and strength of warming‐induced changes to fungal endophytes, we examined fungal leaf and root endophytes in three grassland warming experiments in the US ranging from 2 to 25 years and spanning 2000 km, 12°C of mean annual temperature, and 600 mm of precipitation. We found that experimental warming disrupted symbiosis between plants and fungal endophytes. Colonization of plant tissues by septate fungi decreased in response to warming by 90% in plant leaves and 35% in roots. Warming also reduced fungal diversity and changed community composition in plant leaves, but not roots. The strength, but not direction, of warming effects on fungal endophytes varied by up to 75% among warming experiments. Finally, warming decoupled fungal endophytes from host metabolism by decreasing the correlation between endophyte community and host metabolome dissimilarity. These effects were strongest in the shorter‐term experiment, suggesting endophyte‐host metabolome function may acclimate to warming over decades. Overall, warming‐driven disruption of fungal endophyte community structure and function suggests that this symbiosis may not be a reliable mechanism to promote plant resilience and ameliorate stress responses under global change.

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Detection of a late autumn Karenia papilionacea bloom in Virginia, USA, coastal waters - Jennifer L. Wolny; Michelle C. Tomlinson; Todd A. Egerton; Leah A. Gibala-Smith; Chyna B. Law; Ellen Gortz; Emma W. Brooks; Edward B. Whereat; Margaret R. Mulholland (Harmful Algae, 2025)

Super-Resolving and Denoising 4D flow MRI of Neurofluids Using Physics-Guided Neural Networks - Neal M. Patel; Emily R. Bartusiak; Sean M. Rothenberger; A. J. Schwichtenberg; Edward J. Delp; Vitaliy L. Rayz (Annals of Biomedical Engineering, 2025)

Light buckets and laser beams: mechanisms and applications of photobiomodulation (PBM) therapy - David W. Frankowski; Luigi Ferrucci; Praveen R. Arany; Dawn Bowers; Janis T. Eells; Francisco Gonzalez-Lima; Nicole L. Lohr; Brendan J. Quirk; Harry T. Whelan; Edward G. Lakatta (GeroScience, 2025)
Photobiomodulation (PBM) therapy, a non-thermal light therapy using nonionizing light sources, has shown therapeutic potential across diverse biological processes, including aging and age-associated diseases. In 2023, scientists from the National Institute on Aging (NIA) Intramural and Extramural programs convened a workshop on the topic of PBM to discuss various proposed mechanisms of PBM action, including the stimulation of mitochondrial cytochrome C oxidase, modulation of cell membrane transporters and receptors, and the activation of transforming growth factor-β1. They also reviewed potential therapeutic applications of PBM across a range of conditions, including cardiovascular disease, retinal disease, Parkinson’s disease, and cognitive impairment. Workshop participants largely agreed that PBM holds immense potential as a safe and effective therapeutic approach for a wide range of age-related diseases and cognitive decline. While further research is needed to fully elucidate its mechanisms and optimize treatment protocols, the findings presented at the NIA workshop provide strong evidence for the continued investigation and clinical translation of this promising, inexpensive, safe technology, to aging and age-associated diseases. Here, we review the research presented and discussion held at the meeting. In addition, the text has been updated, where applicable, with recent research findings that have been made since the meeting occurred.

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Global survey of paleo-bedforms on Mars - Matthew Chojnacki; Lori K. Fenton; Lauren A. Edgar; Mackenzie Day; Christopher S. Edwards; Aaron R. Weintraub; Amber L. Gullikson; Matt W. Telfer (Geomorphology, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Place-based climate commissions: embracing messy governmentality - C. Howarth; L. Edwards; A. Duncan; D. Van der Horst; R. Pringle (Climatic Change, 2024)
The role of the ‘place’ in delivering climate action is vital, however much action on climate change locally is fragmented. Independent place-based climate commissions are a novel structure of climate governance developing at the subnational level across cities, regions and counties in the UK. Little is known about these emerging forms of local climate governance and their experiences of navigating ‘mess’ in governance practices and processes. Building on Castán Broto’s framework of messy governmentalities, this paper seeks to assess the capacity of climate commissions to affect meaningful climate mitigation and adaptation action, to understand how they interact with existing climate governance structures and to consider their longer-term sustainability. This paper examines the nature and impact climate commissions have had on local climate action, drawing on qualitative interviews with chairs, commissioners, members of the secretariat and associated local authorities of the Edinburgh, Belfast, Leeds, Surrey, Yorkshire and Humber, and Lincoln commissions in the UK. Analysing the journeys of the commissions through a lens of messy governmentalities, and a focus on bodies, strategies and knowledges within them, we draw out insights on how climate commissions came about, their function and role, their impact and influence, and how they have evolved.

New perspectives on ice forcing in continental arc magma plumbing systems - Brad S. Singer; Pablo Moreno-Yaeger; Meredith Townsend; Christian Huber; Joshua Cuzzone; Benjamin R. Edwards; Matias Romero; Yasmeen Orellana-Salazar; Shaun A. Marcott; Rachel E. Breunig; Ken L. Ferrier; Kathryn Scholz; et al. (Journal of Volcanology and Geothermal Research, 2024)

Assessing impacts of observations on ocean circulation models with examples from coastal, shelf, and marginal seas - Christopher A. Edwards; Pierre De Mey-Frémaux; Bàrbara Barceló-Llull; Guillaume Charria; Byoung-Ju Choi; George R. Halliwell; Lars R. Hole; Colette Kerry; Vassiliki H. Kourafalou; Alexander L. Kurapov; Andrew M. Moore; Baptiste Mourre; et al. (Frontiers in Marine Science, 2024)
Ocean observing systems in coastal, shelf and marginal seas collect diverse oceanographic information supporting a wide range of socioeconomic needs, but observations are necessarily sparse in space and/or time due to practical limitations. Ocean analysis and forecast systems capitalize on such observations, producing data-constrained, four-dimensional oceanographic fields. Here we review efforts to quantify the impact of ocean observations, observing platforms, and networks of platforms on model products of the physical ocean state in coastal regions. Quantitative assessment must consider a variety of issues including observation operators that sample models, error of representativeness, and correlated uncertainty in observations. Observing System Experiments, Observing System Simulation Experiments, representer functions and array modes, observation impacts, and algorithms based on artificial intelligence all offer methods to evaluate data-based model performance improvements according to metrics that characterize oceanographic features of local interest. Applications from globally distributed coastal ocean modeling systems document broad adoption of quantitative methods, generally meaningful reductions in model-data discrepancies from observation assimilation, and support for assimilation of complementary data sets, including subsurface in situ observation platforms, across diverse coastal environments.

Impact of endophyte-infected tall fescue seed consumption on endocrine changes associated with intake regulation and post-absorptive metabolism in growing steers - Mindy E. King; Hannah M. Herzing; Kyle R. McLeod; James L. Klotz; Andrew P. Foote; J. Lannett Edwards; David L. Harmon (Domestic Animal Endocrinology, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Detrending tree-ring widths in closed-canopy forests for climate and disturbance history reconstructions - Daniel L. Druckenbrod; Edward R. Cook; Neil Pederson; Dario Martin-Benito (Dendrochronologia, 2024)

A half-cell reaction approach for pH calculation using a solid-state chloride ion-selective electrode with a hydrogen ion-selective ion-sensitive field effect transistor - S. Fisher Gonski; George W. Luther; Amanda L. Kelley; Todd R. Martz; Elliott G. Roberts; Xinyu Li; Bo Dong; Jordan A. Watson; Taylor S. Wirth; Najid Hussain; Randy J. Feris Serrano; Edward Hale; et al. (Marine Chemistry, 2024)

Microglial inflammation in genome instability: A neurodegenerative perspective - Nina L. Maliar; Emily J. Talbot; Abigail R. Edwards; Svetlana V. Khoronenkova (DNA Repair, 2024)

Red Drum Salinity Tolerance: Comments on Ackerly et al. “Short-Term Salinity Stress During Early Development Impacts the Growth and Survival of Red Drum (Sciaenops ocellatus)” - A. Conway; S. Pauwels; M. Edwards; L. Fontenot; R. Palachek (Estuaries and Coasts, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

The Occurrence of Karenia species in mid-Atlantic coastal waters: Data from the Delmarva Peninsula, USA - Jennifer L. Wolny; Edward B. Whereat; Todd A. Egerton; Leah A. Gibala-Smith; John R. McKay; Judith M. O'Neil; Catherine E. Wazniak; Margaret R. Mulholland (Harmful Algae, 2024)

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Portion size affects food selection in an immersive virtual reality buffet and is related to measured intake in laboratory meals varying in portion size - John W. Long; Sara J. Pritschet; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Barbara J. Rolls; Travis D. Masterson (Appetite, 2023)

Fungal diversity in homes and asthma morbidity among school-age children in New York City - Samuel J. Cochran; Luis Acosta; Adnan Divjan; Angela R. Lemons; Andrew G. Rundle; Rachel L. Miller; Edward Sobek; Brett J. Green; Matthew S. Perzanowski; Karen C. Dannemiller (Environmental Research, 2023)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Icescape‐scale metabolomics reveals cyanobacterial and topographic control of the core metabolism of the cryoconite ecosystem of an Arctic ice cap - Jarishma K. Gokul; Luis A. J. Mur; Andrew J. Hodson; Tristram D. L. Irvine‐Fynn; Aliyah R. Debbonaire; Nozomu Takeuchi; Arwyn Edwards (Environmental Microbiology, 2023)
Glaciers host ecosystems comprised of biodiverse and active microbiota. Among glacial ecosystems, less is known about the ecology of ice caps since most studies focus on valley glaciers or ice sheet margins. Previously we detailed the microbiota of one such high Arctic ice cap, focusing on cryoconite as a microbe‐mineral aggregate formed by cyanobacteria. Here, we employ metabolomics at the scale of an entire ice cap to reveal the major metabolic pathways prevailing in the cryoconite of Foxfonna, central Svalbard. We reveal how geophysical and biotic processes influence the metabolomes of its resident cryoconite microbiota. We observed differences in amino acid, fatty acid, and nucleotide synthesis across the cap reflecting the influence of ice topography and the cyanobacteria within cryoconite. Ice topography influences central carbohydrate metabolism and nitrogen assimilation, whereas bacterial community structure governs lipid, nucleotide, and carotenoid biosynthesis processes. The prominence of polyamine metabolism and nitrogen assimilation highlights the importance of recycling nitrogenous nutrients. To our knowledge, this study represents the first application of metabolomics across an entire ice mass, demonstrating its utility as a tool for revealing the fundamental metabolic processes essential for sustaining life in supraglacial ecosystems experiencing profound change due to Arctic climate change‐driven mass loss.

Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2023)

Adaptation and mitigation capacity of wildland forests in the northeastern United States - Edward K. Faison; Danelle Laflower; Luca L. Morreale; David R. Foster; Brian Hall; Emily Johnson; Jonathan R. Thompson (Forest Ecology and Management, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Aquatic insect accumulation of uranium at spring outflows in the Grand Canyon region as influenced by aqueous and sediment geochemistry and biological factors: implications for monitoring - Daniel J. Cain; Marie-Noële Croteau; Christopher C. Fuller; Kimberly R. Beisner; Kate M. Campbell; Deborah L. Stoliker; Edward R. Schenk (Environmental Monitoring and Assessment, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Challenging the antiquity of the Cradle of Humankind, South Africa: Geochronological evidence restricts the age of Eurotomys bolti and Parapapio to less than 2.3 Ma at Waypoint 160, Bolt's Farm - Tara R. Edwards; Robyn Pickering; Tom L. Mallett; Andy I.R. Herries (Journal of Human Evolution, 2023)

Short-term dynamics of nano- and picoplankton production in an embayment of the southern Benguela upwelling region - Nicole R. Dames; Sina Wallschuss; Emma Rocke; Grant Pitcher; Edward Rybicki; Maya Pfaff; Jessica Burger; Sarah E. Fawcett; Coleen L. Moloney (Estuarine, Coastal and Shelf Science, 2023)

Flow cytometry-based biomarker assay for in vitro identification of microalgal symbionts conferring heat tolerance on corals - Patrick Buerger; Marcin Buler; Heng L. Yeap; Owain R. Edwards; Madeleine J. H. van Oppen; John G. Oakeshott; Leon Court (Frontiers in Marine Science, 2023)
Corals’ tolerance to high temperature stress largely depends on their symbiotic microalgae (Symbiodiniaceae). However, the contributing microalgal traits and their relationships to one another are largely unclear. Here we compare the in vitro cellular profiles of seven Cladocopium C1 acro microalgal strains (derived from the same ancestral strain) during a four-week exposure to 27°C or 31°C. One was an unselected wild-type strain (WT), three were selected at 31°C for nine years and shown to confer thermal tolerance on the coral host (SS+) and three others were similarly selected but did not confer tolerance (SS-). Flow cytometry was used to measure the staining intensities of cells treated with dyes representing the intracellular stress indicators reactive oxygen species (ROS), reduced glutathione (rGSH) and mitochondrial activity, as well as cell size/shape and photosynthetic pigments. Cell densities and photosynthetic efficiency (ϕPSII, F v /F m ) were also measured. WT showed the highest levels of intracellular ROS and mitochondrial activity, lowest rGSH and largest cell sizes at both temperatures. SS+ strains had the lowest ROS and highest rGSH values and a unique pattern of correlations among parameters at 31°C. Our results support previous reports implicating the role of microalgal ROS, mitochondria and rGSH in holobiont thermal tolerance and suggest flow cytometry is a useful screening tool for identifying microalgal strains with enhanced thermal tolerance.

Integrated research in the Arctic – Ecosystem linkages and shifts in the northern Bering Sea and eastern and western Chukchi Sea - Matthew R. Baker; Edward V. Farley; Seth L. Danielson; Calvin Mordy; Kathleen M. Stafford; Danielle M.S. Dickson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Cancer survivorship experiences in Utah: an evaluation assessing indicators of survivors’ quality of life, health behaviors, and access to health services - Morgan M. Millar; Kimberly A. Herget; Blessing Ofori-Atta; Rachel R. Codden; Sandra L. Edwards; Marjorie E. Carter; Brad Belnap; Anne C. Kirchhoff; Carol Sweeney (Cancer Causes & Control, 2023)

Response to: "Are depression and suicidality evolved signals? Evidently, no" - Michael R. Gaffney; Kai H. Adams; Kristen L. Syme; Edward H. Hagen (Evolution and Human Behavior, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

The morphology, functionality, and longevity of a novel all human hepatic cell-based tri-culture system - Jessica R. Weaver; Justin J. Odanga; Kristina K. Wolf; Stephanie Piekos; Mercedes Biven; Mitchell Taub; Jessica LaRocca; Cody Thomas; Alexander Byer-Alcorace; Jingsong Chen; Jung Bok Lee; Edward L. LeCluyse (Toxicology in Vitro, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Detection of numerous phycotoxins in young bull sharks (Carcharhinus leucas) collected from an estuary of national significance - Michelle L. Edwards; Adam M. Schaefer; Malcolm McFarland; Spencer Fire; Christopher R. Perkins; Matthew J. Ajemian (Science of The Total Environment, 2023)

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

Uterine fibroid polygenic risk score (PRS) associates and predicts risk for uterine fibroid - Jacqueline A. Piekos; Jacklyn N. Hellwege; Yanfei Zhang; Eric S. Torstenson; Gail P. Jarvik; Ozan Dikilitas; Iftikhar J. Kullo; Daniel J. Schaid; David R. Crosslin; Sarah A. Pendergrass; Ming Ta Michael Lee; Dan Roden; et al. (Human Genetics, 2022)

More than a whistle: Automated detection of marine sound sources with a convolutional neural network - Ellen L. White; Paul R. White; Jonathan M. Bull; Denise Risch; Suzanne Beck; Ewan W. J. Edwards (Frontiers in Marine Science, 2022)
The effective analysis of Passive Acoustic Monitoring (PAM) data has the potential to determine spatial and temporal variations in ecosystem health and species presence if automated detection and classification algorithms are capable of discrimination between marine species and the presence of anthropogenic and environmental noise. Extracting more than a single sound source or call type will enrich our understanding of the interaction between biological, anthropogenic and geophonic soundscape components in the marine environment. Advances in extracting ecologically valuable cues from the marine environment, embedded within the soundscape, are limited by the time required for manual analyses and the accuracy of existing algorithms when applied to large PAM datasets. In this work, a deep learning model is trained for multi-class marine sound source detection using cloud computing to explore its utility for extracting sound sources for use in marine mammal conservation and ecosystem monitoring. A training set is developed comprising existing datasets amalgamated across geographic, temporal and spatial scales, collected across a range of acoustic platforms. Transfer learning is used to fine-tune an open-source state-of-the-art ‘small-scale’ convolutional neural network (CNN) to detect odontocete tonal and broadband call types and vessel noise (from 0 to 48 kHz). The developed CNN architecture uses a custom image input to exploit the differences in temporal and frequency characteristics between each sound source. Each sound source is identified with high accuracy across various test conditions, including variable signal-to-noise-ratio. We evaluate the effect of ambient noise on detector performance, outlining the importance of understanding the variability of the regional soundscape for which it will be deployed. Our work provides a computationally low-cost, efficient framework for mining big marine acoustic data, for information on temporal scales relevant to the management of marine protected areas and the conservation of vulnerable species.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Genomic regions associated with resistance to soybean rust (Phakopsora pachyrhizi) under field conditions in soybean germplasm accessions from Japan, Indonesia and Vietnam - David R. Walker; Samuel C. McDonald; Donna K. Harris; H. Roger Boerma; James W. Buck; Edward J. Sikora; David B. Weaver; David L. Wright; James J. Marois; Zenglu Li (Theoretical and Applied Genetics, 2022)
Key message Eight soybean genomic regions, including six never before reported, were found to be associated with resistance to soybean rust ( Phakopsora pachyrhizi ) in the southeastern USA. Abstract Soybean rust caused by Phakopsora pachyrhizi is one of the most important foliar diseases of soybean [ Glycine max (L.) Merr.]. Although seven Rpp resistance gene loci have been reported, extensive pathotype variation in and among fungal populations increases the importance of identifying additional genes and loci associated with rust resistance. One hundred and ninety-one soybean plant introductions from Japan, Indonesia and Vietnam, and 65 plant introductions from other countries were screened for resistance to P. pachyrhizi under field conditions in the southeastern USA between 2008 and 2015. The results indicated that 84, 69, and 49% of the accessions from southern Japan, Vietnam or central Indonesia, respectively, had negative BLUP values, indicating less disease than the panel mean. A genome-wide association analysis using SoySNP50K Infinium BeadChip data identified eight genomic regions on seven chromosomes associated with SBR resistance, including previously unreported regions of Chromosomes 1, 4, 6, 9, 13, and 15, in addition to the locations of the Rpp3 and Rpp6 loci. The six unreported genomic regions might contain novel Rpp loci. The identification of additional sources of rust resistance and associated genomic regions will further efforts to develop soybean cultivars with broad and durable resistance to soybean rust in the southern USA.

Fates of petroleum during the deepwater horizon oil spill: A chemistry perspective - Edward B. Overton; Puspa L. Adhikari; Jagoš R. Radović; Uta Passow (Frontiers in Marine Science, 2022)
We describe the initial bulk and compound specific composition of the liquid oil spilled during the Deepwater Horizon (DwH) disaster. The emphasis is on the target hydrocarbon compounds typically found in highest concentrations and on those of concern from a toxicological perspective (i.e., the target normal alkanes and isoprenoids, and PAHs on U.S. Environmental Protection Agency’s (EPA) priority list with their alkyl homolog compounds), and/or those relevant for forensic fingerprinting of spill residues (i.e., sulfur containing PAHs and biomarker compounds). Weathering changed the oil’s composition in various environmental compartments. These compositional changes and potential environmental impacts of the remaining weathered residues are presented in this paper. Biodegradation occurred in both surface and subsurface environments while photooxidation primarily modified and removed hydrocarbons in floating oil slicks. The volatile, soluble and highly labile C 1 to C 10 hydrocarbons were rapidly degraded in the water column and/or emitted to the atmosphere (evaporation). The semi-volatile hydrocarbons (labile C 10 to C 25 ) that remained in the water column and floating oil on the water’s surface were lost from oil residues during weathering. The heavy nonvolatile and insoluble hydrocarbons (recalcitrant C 25 +) were least affected by initial weathering processes in 2010. The composition of the residual oil fraction in surface floating oil was further altered by the addition of oil soluble oxy hydrocarbons produced from photooxidation. During 2011 and 2012 the resulting highly insoluble recalcitrant C 25 + oily residues remained on the shorelines, bottom sediments, or bound to suspended particulates in the water column, with detectable residues mostly returning to near pre-spill levels by 2015 to 2020. Some recalcitrant oil residues can still be found at various locations, including some coastal environments (e.g., marshes), or deep-water sediments, at very low levels, ten years after the spill.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Resolving taxonomic confusion: establishing the genus Phytobacter on the list of clinically relevant Enterobacteriaceae - Theo H. M. Smits; Lavinia N. V. S. Arend; Sofia Cardew; Erika Tång-Hallbäck; Marcelo T. Mira; Edward R. B. Moore; Jorge L. M. Sampaio; Fabio Rezzonico; Marcelo Pillonetto (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although many clinically significant strains belonging to the family Enterobacteriaceae fall into a restricted number of genera and species, there is still a substantial number of isolates that elude this classification and for which proper identification remains challenging. With the current improvements in the field of genomics, it is not only possible to generate high-quality data to accurately identify individual nosocomial isolates at the species level and understand their pathogenic potential but also to analyse retrospectively the genome sequence databases to identify past recurrences of a specific organism, particularly those originally published under an incorrect or outdated taxonomy. We propose a general use of this approach to classify further clinically relevant taxa, i.e., Phytobacter spp., that have so far gone unrecognised due to unsatisfactory identification procedures in clinical diagnostics. Here, we present a genomics and literature-based approach to establish the importance of the genus Phytobacter as a clinically relevant member of the Enterobacteriaceae family.

Temporal Baseline of Essesntial and Non-essential Elements Recorded in Baleen of Western Arctic Bowhead Whale (Balaena mysticetus) - Samantha L. Shore; Dimitrios G. Giarikos; Lawrence K. Duffy; Mickie R. Edwards; Amy C. Hirons (Bulletin of Environmental Contamination and Toxicology, 2022)
This study established the first baseline of changing elemental concentrations in bowhead whale baleen over time (1958–1999). From previously published stable isotope data, year, season (summer or winter), and location (Beaufort or Bering/Chukchi seas) were attributed to each sample. Thirteen elements (Al, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, V, Zn) in baleen from nine subsistence-harvested bowhead whales (n = 138) were detected. Al, Cu, and Fe were the highest concentrations while Cd and V were among the lowest. Our data supports absorption as the main route of exposure to environmental elements rather than biomagnification due to bowhead whales’ low trophic position. A linear mixed-effects model confirmed most elements’ concentrations increased with time, while location and sex were insignificant explanatory factors. These temporal fluctuations were most likely a product of environmental changes due to a warming climate and human activities.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Expanding the horizon of research into the pathogenesis of the white matter diseases: Proceedings of the 2021 Annual Workshop of the Albert Research Institute for White Matter and Cognition - Shawn N. Whitehead; Askiel Bruno; Jeffrey M. Burns; S. Thomas Carmichael; Anna Csiszar; Jodi D. Edwards; Fanny M. Elahi; Giuseppe Faraco; Douglas B. Gould; Deborah R. Gustafson; Vladimir Hachinski; Gary Rosenberg; et al. (GeroScience, 2022)

Sea-Level Rise: From Global Perspectives to Local Services - Gaël Durand; Michiel R. van den Broeke; Goneri Le Cozannet; Tamsin L. Edwards; Paul R. Holland; Nicolas C. Jourdain; Ben Marzeion; Ruth Mottram; Robert J. Nicholls; Frank Pattyn; Frank Paul; Aimée B. A. Slangen; et al. (Frontiers in Marine Science, 2022)
Coastal areas are highly diverse, ecologically rich, regions of key socio-economic activity, and are particularly sensitive to sea-level change. Over most of the 20th century, global mean sea level has risen mainly due to warming and subsequent expansion of the upper ocean layers as well as the melting of glaciers and ice caps. Over the last three decades, increased mass loss of the Greenland and Antarctic ice sheets has also started to contribute significantly to contemporary sea-level rise. The future mass loss of the two ice sheets, which combined represent a sea-level rise potential of ∼65 m, constitutes the main source of uncertainty in long-term (centennial to millennial) sea-level rise projections. Improved knowledge of the magnitude and rate of future sea-level change is therefore of utmost importance. Moreover, sea level does not change uniformly across the globe and can differ greatly at both regional and local scales. The most appropriate and feasible sea level mitigation and adaptation measures in coastal regions strongly depend on local land use and associated risk aversion. Here, we advocate that addressing the problem of future sea-level rise and its impacts requires (i) bringing together a transdisciplinary scientific community, from climate and cryospheric scientists to coastal impact specialists, and (ii) interacting closely and iteratively with users and local stakeholders to co-design and co-build coastal climate services, including addressing the high-end risks.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Evidence that geographic variation in genetic ancestry associates with uterine fibroids - Jacob M. Keaton; Elizabeth A. Jasper; Jacklyn N. Hellwege; Sarah H. Jones; Eric S. Torstenson; Todd L. Edwards; Digna R. Velez Edwards (Human Genetics, 2021)

Correction to: Latitudinal variation in monthly-scale reproductive synchrony among Acropora coral assemblages in the Indo-Pacific - Jessica Bouwmeester; Alasdair J. Edwards; James R. Guest; Andrew G. Bauman; Michael L. Berumen; Andrew H. Baird (Coral Reefs, 2021)

Latitudinal variation in monthly-scale reproductive synchrony among Acropora coral assemblages in the Indo-Pacific - Jessica Bouwmeester; Alasdair J. Edwards; James R. Guest; Andrew G. Bauman; Michael L. Berumen; Andrew H. Baird (Coral Reefs, 2021)
Early research into coral reproductive biology suggested that spawning synchrony was driven by variations in the amplitude of environmental variables that are correlated with latitude, with synchrony predicted to break down at lower latitudes. More recent research has revealed that synchronous spawning, both within and among species, is a feature of all speciose coral assemblages, including equatorial reefs. Nonetheless, considerable variation in reproductive synchrony exists among locations and the hypothesis that the extent of spawning synchrony is correlated with latitude has not been formally tested on a large scale. Here, we use data from 90 sites throughout the Indo-Pacific and a quantitative index of reproductive synchrony applied at a monthly scale to demonstrate that, despite considerable spatial and temporal variation, there is no correlation between latitude and reproductive synchrony. Considering the critical role that successful reproduction plays in the persistence and recovery of coral reefs, research is urgently needed to understand the drivers underpinning variation in reproductive synchrony.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Assessment of the efficacy of six field cleaning protocols for hydrocarbon quantification - Emily C. Pisarski; Edward F. Wirth; Paul L. Pennington; Ian Hartwell; Brian S. Shaddrix; David R. Whitall; Dennis A. Apeti; Gregory Baker (Environmental Science and Pollution Research, 2021)

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

Microbial biogeography through the lens of exotic species: the recent introduction and spread of the freshwater diatom Discostella asterocostata in the United States - Andrew J. Alverson; Tyler K. Chafin; Kiley A. Jones; Kalina M. Manoylov; Hillary Johnson; Matthew L. Julius; Teofil Nakov; Elizabeth C. Ruck; Edward C. Theriot; Kevin M. Yeager; Jeffery R. Stone (Biological Invasions, 2021)

Recent progress on combining geomorphological and geochronological data with ice sheet modelling, demonstrated using the last British–Irish Ice Sheet - Jeremy C. Ely; Chris D. Clark; Richard C. A. Hindmarsh; Anna L. C. Hughes; Sarah L. Greenwood; Sarah L. Bradley; Edward Gasson; Lauren Gregoire; Niall Gandy; Chris R. Stokes; David Small (Journal of Quaternary Science, 2021)
Palaeo‐ice sheets are important analogues for understanding contemporary ice sheets, offering a record of ice sheet behaviour that spans millennia. There are two main approaches to reconstructing palaeo‐ice sheets. Empirical reconstructions use the available glacial geological and chronological evidence to estimate ice sheet extent and dynamics but lack direct consideration of ice physics. In contrast, numerically modelled simulations implement ice physics, but often lack direct quantitative comparison with empirical evidence. Despite being long identified as a fruitful scientific endeavour, few ice sheet reconstructions attempt to reconcile the empirical and model‐based approaches. To achieve this goal, model‐data comparison procedures are required. Here, we compare three numerically modelled simulations of the former British–Irish Ice Sheet with the following lines of evidence: (a) position and shape of former margin positions, recorded by moraines; (b) former ice‐flow direction and flow‐switching, recorded by flowsets of subglacial bedforms; and (c) the timing of ice‐free conditions, recorded by geochronological data. These model–data comparisons provide a useful framework for quantifying the degree of fit between numerical model simulations and empirical constraints. Such tools are vital for reconciling numerical modelling and empirical evidence, the combination of which will lead to more robust palaeo‐ice sheet reconstructions with greater explicative and ultimately predictive power.

MRI-based Parcellation and Morphometry of the Individual Rhesus Monkey Brain: the macaque Harvard-Oxford Atlas (mHOA), a translational system referencing a standardized ontology - R. Jarrett Rushmore; Sylvain Bouix; Marek Kubicki; Yogesh Rathi; Douglas L. Rosene; Edward H. Yeterian; Nikos Makris (Brain Imaging and Behavior, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

An Experimental Framework for Selectively Breeding Corals for Assisted Evolution - Adriana Humanes; Elizabeth A. Beauchamp; John C. Bythell; Mitch K. Carl; Jamie R. Craggs; Alasdair J. Edwards; Yimnang Golbuu; Liam Lachs; Helios M. Martinez; Pawel Palmowski; Faith Paysinger; Janna L. Randle; et al. (Frontiers in Marine Science, 2021)
Coral cover on tropical reefs has declined during the last three decades due to the combined effects of climate change, destructive fishing, pollution, and land use change. Drastic reductions in greenhouse gas emissions combined with effective coastal management and conservation strategies are essential to slow this decline. Innovative approaches, such as selective breeding for adaptive traits combined with large-scale sexual propagation, are being developed with the aim of pre-adapting reefs to increased ocean warming. However, there are still major gaps in our understanding of the technical and methodological constraints to producing corals for such restoration interventions. Here we propose a framework for selectively breeding corals and rearing them from eggs to 2.5-year old colonies using the coral Acropora digitifera as a model species. We present methods for choosing colonies for selective crossing, enhancing early survivorship in ex situ and in situ nurseries, and outplanting and monitoring colonies on natal reefs. We used a short-term (7-day) temperature stress assay to select parental colonies based on heat tolerance of excised branches. From six parental colonies, we produced 12 distinct crosses, and compared survivorship and growth of colonies transferred to in situ nurseries or outplanted to the reef at different ages. We demonstrate that selectively breeding and rearing coral colonies is technically feasible at small scales and could be upscaled as part of restorative assisted evolution initiatives. Nonetheless, there are still challenges to overcome before selective breeding can be implemented as a viable conservation tool, especially at the post-settlement and outplanting phases. Although interdisciplinary approaches will be needed to overcome many of the challenges identified in this study, selective breeding has the potential to be a viable tool within a reef managers toolbox to support the persistence of selected reefs in the face of climate change.

Macroecological patterns of forest structure and allometric scaling in mangrove forests - Andre S. Rovai; Robert R. Twilley; Edward Castañeda‐Moya; Stephen R. Midway; Daniel A. Friess; Carl C. Trettin; Jacob J. Bukoski; Atticus E.L. Stovall; Paulo R. Pagliosa; Alessandra L. Fonseca; Richard A. Mackenzie; Aslan Aslan; et al. (Global Ecology and Biogeography, 2021)
Aim Mangrove wetlands span broad geographical gradients, resulting in functionally diverse tree communities. We asked whether latitudinal variation, allometric scaling relationships and species composition influence mangrove forest structure and biomass allocation across biogeographical regions and distinct coastal morphologies. Location Global. Time period Present. Major taxa studied Mangrove ecosystems. Methods We built the largest field‐based dataset on mangrove forest structure and biomass to date ( c . 2,800 plots from 67 countries) to address macroecological questions pertaining to structural and functional diversity of mangroves spanning biogeographical and coastal morphology gradients. We used frequentist inference statistics and machine learning models to determine environmental drivers that control biomass allocation within and across mangrove communities globally. Results Allometric scaling relationships and forest structural complexity were consistent across biogeographical and coastal morphology gradients, suggesting that mangrove biomass is controlled by regional forcings rather than by latitude or species composition. For instance, nearly 40% of the global variation in biomass was explained by regional climate and hydroperiod, revealing nonlinear thresholds that control biomass accumulation across broad geographical gradients. Furthermore, we found that ecosystem‐level carbon stocks (average 401 ± 48 MgC/ha, covering biomass and the top 1 m of soil) varied little across diverse coastal morphologies, reflecting regional bottom‐up geomorphic controls that shape global patterns in mangrove biomass apportioning. Main conclusions Our findings reconcile views of wetland and terrestrial forest macroecology. Similarities in stand structural complexity and cross‐site size–density relationships across multiscale environmental gradients show that resource allocation in mangrove ecosystems is independent of tree size and invariant to species composition or latitude. Mangroves follow a universal fractal‐based scaling relationship that describes biomass allocation for several other terrestrial tree‐dominated communities. Understanding how mangroves adhere to these universal allometric rules can improve our ability to account for biomass apportioning and carbon stocks in response to broad geographical gradients.

Ecosystem Recovery from Disturbance is Constrained by N Cycle Openness, Vegetation-Soil N Distribution, Form of N Losses, and the Balance Between Vegetation and Soil-Microbial Processes - Edward B. Rastetter; George W. Kling; Gaius R. Shaver; Byron C. Crump; Laura Gough; Kevin L. Griffin (Ecosystems, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Are physiological and behavioural responses to stressors displayed concordantly by wild urban rodents? - Loren L. Fardell; Miguel A. Bedoya-Pérez; Christopher R. Dickman; Mathew S. Crowther; Chris R. Pavey; Edward J. Narayan (The Science of Nature, 2021)
Understanding wild animal responses to stressors underpins effective wildlife management. In order for responses to stressors to be correctly interpreted, it is critical that measurements are taken on wild animals using minimally invasive techniques. Studies investigating wild animal responses to stressors often measure either a single physiological or behavioural variable, but whether such responses are comparable and concordant remains uncertain. We investigated this question in a pilot study that measured responses of wild-caught urban brown and black rats ( Rattus norvegicus , Rattus rattus ) to fur-based olfactory cues from a predator, the domestic cat ( Felis catus ); a novel herbivore, the koala ( Phascolarctos cinereus ); and a familiar herbivore and competitor, the common brushtail possum ( Trichosurus vulpecula ). Physiological responses, measured by assaying faecal glucocorticoid metabolites, were compared to behavioural responses observed via video recordings. We found that physiological and behavioural responses to stressors were expressed concordantly. There was no sizeable physiological response observed, and the behavioural response when considered across the night was negligible. However, the behavioural response to the predator and competitor cues changed across the observation period, with activity increasing with increasing hours of exposure. Our results indicate that responses of wild rodents to cues are nuanced, with stress responses modulated by behaviour changes that vary over time according to the severity of the perceived threat as animals gather further information. If the physiological response alone had been assessed, this moderated response may not have been evident, and in terms of wildlife management, vital information would have been lost.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

APPA (apocynin and paeonol) modulates pathological aspects of human neutrophil function, without supressing antimicrobial ability, and inhibits TNFα expression and signalling - A. L. Cross; J. Hawkes; H. L. Wright; R. J. Moots; S. W. Edwards (Inflammopharmacology, 2020)
Neutrophils are key players in the pathophysiological process underlying inflammatory conditions not only by release of tissue-damaging cytotoxic enzymes, reactive oxygen species (ROS) but also by secretion of important immunomodulatory chemokines and cytokines. Here, we report the effects of the novel agent APPA, undergoing formal clinical development for treatment of osteoarthritis, and its constituent components, apocynin (AP) and paeonol (PA) on a number of neutrophil functions, including effects on TNFα- expression and signalling. Neutrophils were treated with APPA (10–1000 µg/mL) prior to the measurement of cell functions, including ROS production, chemotaxis, apoptosis and surface receptor expression. Expression levels of several key genes and proteins were measured after incubation with APPA and the chromatin re-modelling agent, R848. APPA did not significantly affect phagocytosis, bacterial killing or expression of surface receptors, while chemotactic migration was affected only at the highest concentrations. However, APPA down-regulated neutrophil degranulation and ROS levels, and decreased the formation of neutrophil extracellular traps. APPA also decreased cytokine-stimulated gene expression, inhibiting both TNFα- and GM-CSF-induced cell signalling. APPA was as effective as infliximab in down-regulating chemokine and IL-6 expression following incubation with R848. Whilst APPA does not interfere with neutrophil host defence against infections, it does inhibit neutrophil degranulation, and cytokine-driven signalling pathways (e.g. autocrine signalling and NF-κB activation), processes that are associated with inflammation. These observations may explain the mechanisms by which APPA exerts anti-inflammatory effects and suggests a potential therapeutic role in inflammatory diseases in which neutrophils and TNFα signalling are important in pathology, such as rheumatoid arthritis.

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

Taxonomy of prokaryotic viruses: 2018-2019 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Evelien M. Adriaenssens; Matthew B. Sullivan; Petar Knezevic; Leonardo J. van Zyl; B. L. Sarkar; Bas E. Dutilh; Poliane Alfenas-Zerbini; Małgorzata Łobocka; Yigang Tong; James Rodney Brister; Andrea I. Moreno Switt; Jochen Klumpp; et al. (Archives of Virology, 2020)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

The integration of grain-size distribution and plasticity parameters for characterizing and classifying unconsolidated fine-grained sediments - Wisam R. Muttashar; L. Sebastian Bryson; Michael McGlue; Edward Woolery (Bulletin of Engineering Geology and the Environment, 2020)

Conservation genetics of Madagascar’s critically endangered ploughshare tortoise (Astrochelys yniphora) - Angelo R. Mandimbihasina; Cynthia L. Frasier; Ryan A. Hagenson; Brittani A. D. Robertson; Shannon E. Engberg; Richard E. Lewis; Lance G. Woolaver; Emilienne Razafimahatratra; Lydia L. Rabetafika; Edward E. Louis (Conservation Genetics, 2020)

Predicting Patient Reported Outcomes of Cognitive Function Using Connectome-Based Predictive Modeling in Breast Cancer - Ashley M. Henneghan; Chris Gibbons; Rebecca A. Harrison; Melissa L. Edwards; Vikram Rao; Douglas W. Blayney; Oxana Palesh; Shelli R. Kesler (Brain Topography, 2020)

Complete genome sequence of bovine herpesvirus type 1.1 (BoHV-1.1) Los Angeles (LA) strain and its genotypic relationship to BoHV-1.1 Cooper and more recently isolated wild-type field strains - Jean M. d’Offay; Robert W. Fulton; R. Eberle; Edward J. Dubovi; Christopher C. L. Chase (Archives of Virology, 2019)

Elevated carbon dioxide decreases the adverse effects of higher temperature and drought stress by mitigating oxidative stress and improving water status in Arabidopsis thaliana - Mohammad I. Abo Gamar; Anna Kisiala; R. J. Neil Emery; Edward C. Yeung; Sophia L. Stone; Mirwais M. Qaderi (Planta, 2019)

Environmental heterogeneity and not vicariant biogeographic barriers generate community‐wide population structure in desert‐adapted snakes - Edward A. Myers; Alexander T. Xue; Marcelo Gehara; Christian L. Cox; Alison R. Davis Rabosky; Julio Lemos‐Espinal; Juan E. Martínez‐Gómez; Frank T. Burbrink (Molecular Ecology, 2019)
Genetic structure can be influenced by local adaptation to environmental heterogeneity and biogeographic barriers, resulting in discrete population clusters. Geographic distance among populations, however, can result in continuous clines of genetic divergence that appear as structured populations. Here, we evaluate the relevant importance of these three factors over a landscape characterized by environmental heterogeneity and the presence of a hypothesized biogeographic barrier in producing population genetic structure within 13 codistributed snake species using a genomic data set. We demonstrate that geographic distance and environmental heterogeneity across western North America contribute to population genomic divergence. Surprisingly, landscape features long thought to contribute to biogeographic barriers play little role in divergence community wide. Our results suggest that isolation by environment is the most important contributor to genomic divergence. Furthermore, we show that models of population clustering that incorporate spatial information consistently outperform nonspatial models, demonstrating the importance of considering geographic distances in population clustering. We argue that environmental and geographic distances as drivers of community‐wide divergence should be explored before assuming the role of biogeographic barriers.

Characterisation of the effect of day length, and associated differences in dietary intake, on the gut microbiota of Soay sheep - Nadine A. Thomas; Andrea M. Olvera-Ramírez; Leticia Abecia; Clare L. Adam; Joan E. Edwards; Georgina F. Cox; Patricia A. Findlay; Elodie Destables; Tracy A. Wood; Neil R. McEwan (Archives of Microbiology, 2019)

Epidemiological Investigation of Toxoplasma gondii Infections in Commercial Sheep Flock in an Endemic Area for Ocular Toxoplasmosis in Southern Brazil - Angélica Consalter; Edwards Frazão-Teixeira; Jitender P. Dubey; Eraldo L. Zanella; Andressa F. da Silva; Guilherme N. de Souza; Ana M. R. Ferreira (Acta Parasitologica, 2019)

Microbiological safety of popular recreation swimming sites in Central California - Xunde Li; Jennifer A. Chase; Ronald F. Bond; Panachon Lor; Kristine Fernandez; Trân H. Nguyen; Melissa L. Partyka; Anyarat Thiptara; Edward R. Atwill (Environmental Monitoring and Assessment, 2019)

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Inbreeding tolerance as a pre‐adapted trait for invasion success in the invasive ant Brachyponera chinensis - Pierre‐André Eyer; Kenji Matsuura; Edward L. Vargo; Kazuya Kobayashi; Toshihisa Yashiro; Wataru Suehiro; Chihiro Himuro; Tomoyuki Yokoi; Benoit Guénard; Robert R. Dunn; Kazuki Tsuji (Molecular Ecology, 2018)
Identifying traits that facilitate species introductions and successful invasions of ecosystems represents a key issue in ecology. Following their establishment into new environments, many non‐native species exhibit phenotypic plasticity with post‐introduction changes in behaviour, morphology or life history traits that allow them to overcome the presumed loss of genetic diversity resulting in inbreeding and reduced adaptive potential. Here, we present a unique strategy in the invasive ant Brachyponera chinensis (Emery) , in which inbreeding tolerance is a pre‐adapted trait for invasion success, allowing this ant to cope with genetic depletion following a genetic bottleneck. We report for the first time that inbreeding is not a consequence of the founder effect following introduction, but it is due to mating between sister queens and their brothers that pre‐exists in native populations which may have helped it circumvent the cost of invasion. We show that a genetic bottleneck does not affect the genetic diversity or the level of heterozygosity within colonies and suggest that generations of sib‐mating in native populations may have reduced inbreeding depression through purifying selection of deleterious alleles. This work highlights how a unique life history may pre‐adapt some species for biological invasions.

Does sowing an oats catch crop reduce nitrate leaching from urine deposition following simulated winter forage grazing? - a growth chamber experiment - P. L. Carey; K. C. Cameron; H. J. Di; G. R. Edwards (Plant and Soil, 2018)

Muscle health and performance in monozygotic twins with 30 years of discordant exercise habits - Katherine E. Bathgate; James R. Bagley; Edward Jo; Robert J. Talmadge; Irene S. Tobias; Lee E. Brown; Jared W. Coburn; Jose A. Arevalo; Nancy L. Segal; Andrew J. Galpin (European Journal of Applied Physiology, 2018)

High‐resolution reconstruction of 8.2‐ka BP event documented in Père Noël cave, southern Belgium - M. Allan; N. Fagel; H. J. L. van der Lubbe; H. B. Vonhof; H. Cheng; R. Lawrence Edwards; S. Verheyden (Journal of Quaternary Science, 2018)
A distinct shift in δ 18 O, δ 13 C and trace element contents of the Père Noël (PN) stalagmite from southern Belgium revealed an abrupt climatic anomaly at 8.13 ± 0.03 ka BP (before present = before 1950 AD). This anomaly is characterized by a maximum drop in the δ 18 O (−1.4‰ compared the mean) between 8.13 and 8.10 ka BP (±0.03). This drop of δ 18 O coincides with a decrease in δ 13 C and trace element (Sr, Ba and Mg) concentrations suggesting drier conditions. Our precise chronology provides the timing of the outburst of proglacial lakes Agassiz and Ojibway that caused the δ 18 O, δ 13 C and trace elemental anomalies at 8.13–8.10 ± 0.03 ka BP, which corresponds to the 8.2‐ka BP event. The PN stalagmite bears δ 18 O values in fluid inclusions that covary with the δ 18 O values in calcite, suggesting that the speleothem calcite δ 18 O primarily reflects variations in the rainfall δ 18 O. Comparison of the PN record with different marine and terrestrial archives during the 8.2‐ka BP event shows a good agreement in timing and duration, suggesting that the PN speleothem can be regarded as a valuable proxy to better understand the 8.2‐ka BP event.

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Glacial and interglacials in the Neotropics: a 130,000-year diatom record from central Panama - C. R. Shadik; G. M. Cárdenes-Sandí; A. Correa-Metrio; R. L. Edwards; A. Min; M. B. Bush (Journal of Paleolimnology, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Music as an Adjunct to Opioid-Based Analgesia - Peter R. Chai; Stephanie Carreiro; Megan L. Ranney; Ketki Karanam; Marko Ahtisaari; Robert Edwards; Kristin L. Schreiber; Lubabah Ben-Ghaly; Timothy B. Erickson; Edward W. Boyer (Journal of Medical Toxicology, 2017)

Feedbacks between plant N demand and rhizosphere priming depend on type of mycorrhizal association - Benjamin N. Sulman; Edward R. Brzostek; Chiara Medici; Elena Shevliakova; Duncan N. L. Menge; Richard P. Phillips (Ecology Letters, 2017)
Ecosystem carbon (C) balance is hypothesised to be sensitive to the mycorrhizal strategies that plants use to acquire nutrients. To test this idea, we coupled an optimality‐based plant nitrogen (N) acquisition model with a microbe‐focused soil organic matter ( SOM ) model. The model accurately predicted rhizosphere processes and C–N dynamics across a gradient of stands varying in their relative abundance of arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) trees. When mycorrhizal dominance was switched – ECM trees dominating plots previously occupied by AM trees, and vice versa – legacy effects were apparent, with consequences for both C and N stocks in soil. Under elevated productivity, ECM trees enhanced decomposition more than AM trees via microbial priming of unprotected SOM . Collectively, our results show that ecosystem responses to global change may hinge on the balance between rhizosphere priming and SOM protection, and highlight the importance of dynamically linking plants and microbes in terrestrial biosphere models.

Ensemble Decision Tree Models Using RUSBoost for Estimating Risk of Iron Failure in Drinking Water Distribution Systems - S. R. Mounce; K. Ellis; J. M. Edwards; V. L. Speight; N. Jakomis; J. B. Boxall (Water Resources Management, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Role of polysaccharides in food, digestion, and health - A. Lovegrove; C. H. Edwards; I. De Noni; H. Patel; S. N. El; T. Grassby; C. Zielke; M. Ulmius; L. Nilsson; P. J. Butterworth; P. R Ellis; P. R. Shewry (Critical Reviews in Food Science and Nutrition, 2017)

Losing Legacies, Ecological Release, and Transient Responses: Key Challenges for the Future of Northern Ecosystem Science - Merritt R. Turetsky; Jennifer L. Baltzer; Jill F. Johnstone; Michelle C. Mack; Kevin McCann; Edward A. G. Schuur (Ecosystems, 2017)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Use of a coupled soil-root-leaf model to optimise phosphate fertiliser use efficiency in barley - J. Heppell; S. Payvandi; P. Talboys; K. C. Zygalakis; D. Langton; R. Sylvester-Bradley; A. C. Edwards; R. Walker; P. Withers; D. L. Jones; T. Roose (Plant and Soil, 2016)

Biogeographic gradients in ecosystem processes of the invasive ecosystem engineer Phragmites australis - A. Randall Hughes; Forest R. Schenck; Jeanne Bloomberg; Torrance C. Hanley; Dongmei Feng; Tarik C. Gouhier; R. Edward Beighley; David L. Kimbro (Biological Invasions, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Taxon interactions control the distributions of cryoconite bacteria colonizing a High Arctic ice cap - Jarishma K. Gokul; Andrew J. Hodson; Eli R. Saetnan; Tristram D. L. Irvine‐Fynn; Philippa J. Westall; Andrew P. Detheridge; Nozomu Takeuchi; Jennifer Bussell; Luis A. J. Mur; Arwyn Edwards (Molecular Ecology, 2016)
Microbial colonization of glacial ice surfaces incurs feedbacks which affect the melting rate of the ice surface. Ecosystems formed as microbe–mineral aggregates termed cryoconite locally reduce ice surface albedo and represent foci of biodiversity and biogeochemical cycling. Consequently, greater understanding the ecological processes in the formation of functional cryoconite ecosystems upon glacier surfaces is sought. Here, we present the first bacterial biogeography of an ice cap, evaluating the respective roles of dispersal, environmental and biotic filtration occurring at local scales in the assembly of cryoconite microbiota. 16S rRNA gene amplicon semiconductor sequencing of cryoconite colonizing a Svalbard ice cap coupled with digital elevation modelling of physical parameters reveals the bacterial community is dominated by a ubiquitous core of generalist taxa, with evidence for a moderate pairwise distance–decay relationship. While geographic position and melt season duration are prominent among environmental predictors of community structure, the core population of taxa appears highly influential in structuring the bacterial community. Taxon co‐occurrence network analysis reveals a highly modular community structured by positive interactions with bottleneck taxa, predominantly Actinobacteria affiliated to isolates from soil humus. In contrast, the filamentous cyanobacterial taxon (assigned to Leptolyngbya/Phormidesmis pristleyi ) which dominates the community and binds together granular cryoconite are poorly connected to other taxa. While our study targeted one ice cap, the prominent role of generalist core taxa with close environmental relatives across the global cryosphere indicate discrete roles for cosmopolitan Actinobacteria and Cyanobacteria as respective keystone taxa and ecosystem engineers of cryoconite ecosystems colonizing ice caps.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

The 12-day thermoregulatory metamorphosis of Red-winged Blackbirds (Agelaius phoeniceus) - Sarah K. Goy Sirsat; Tushar S. Sirsat; Janna L. Crossley; Paul R. Sotherland; Edward M. Dzialowski (Journal of Comparative Physiology B, 2016)

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Metformin and prostate cancer mortality: a meta-analysis - Konrad H. Stopsack; David R. Ziehr; Jennifer R. Rider; Edward L. Giovannucci (Cancer Causes & Control, 2016)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

A pan‐Arctic synthesis of CH 4 and CO 2 production from anoxic soil incubations - Claire C. Treat; Susan M. Natali; Jessica Ernakovich; Colleen M. Iversen; Massimo Lupascu; Anthony David McGuire; Richard J. Norby; Taniya Roy Chowdhury; Andreas Richter; Hana Šantrůčková; Christina Schädel; Edward A. G. Schuur; et al. (Global Change Biology, 2015)
Permafrost thaw can alter the soil environment through changes in soil moisture, frequently resulting in soil saturation, a shift to anaerobic decomposition, and changes in the plant community. These changes, along with thawing of previously frozen organic material, can alter the form and magnitude of greenhouse gas production from permafrost ecosystems. We synthesized existing methane (CH 4 ) and carbon dioxide (CO 2 ) production measurements from anaerobic incubations of boreal and tundra soils from the geographic permafrost region to evaluate large‐scale controls of anaerobic CO 2 and CH 4 production and compare the relative importance of landscape‐level factors (e.g., vegetation type and landscape position), soil properties (e.g., pH, depth, and soil type), and soil environmental conditions (e.g., temperature and relative water table position). We found fivefold higher maximum CH 4 production per gram soil carbon from organic soils than mineral soils. Maximum CH 4 production from soils in the active layer (ground that thaws and refreezes annually) was nearly four times that of permafrost per gram soil carbon, and CH 4 production per gram soil carbon was two times greater from sites without permafrost than sites with permafrost. Maximum CH 4 and median anaerobic CO 2 production decreased with depth, while CO 2 :CH 4 production increased with depth. Maximum CH 4 production was highest in soils with herbaceous vegetation and soils that were either consistently or periodically inundated. This synthesis identifies the need to consider biome, landscape position, and vascular/moss vegetation types when modeling CH 4 production in permafrost ecosystems and suggests the need for longer‐term anaerobic incubations to fully capture CH 4 dynamics. Our results demonstrate that as climate warms in arctic and boreal regions, rates of anaerobic CO 2 and CH 4 production will increase, not only as a result of increased temperature, but also from shifts in vegetation and increased ground saturation that will accompany permafrost thaw.

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

Coinfection with multiple strains of bovine papular stomatitis virus - Tao Huang; Edan R. Tulman; Diego G. Diel; Sushil Khatiwada; Will Sims; John F. Edwards; Xintian Wen; Gerald F. Kutish; Daniel L. Rock; Gustavo Delhon (Archives of Virology, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

The Virtual Toxicology Service: Wearable Head-Mounted Devices for Medical Toxicology - Peter R. Chai; Roger Y. Wu; Megan L. Ranney; Paul S. Porter; Kavita M. Babu; Edward W. Boyer (Journal of Medical Toxicology, 2014)

Admixture mapping identifies a locus at 15q21.2–22.3 associated with keloid formation in African Americans - Digna R. Velez Edwards; Krystal S. Tsosie; Scott M. Williams; Todd L. Edwards; Shirley B. Russell (Human Genetics, 2014)

Cryptic structure and niche divergence within threatened Galápagos giant tortoises from southern Isabela Island - D. L. Edwards; R. C. Garrick; W. Tapia; A. Caccone (Conservation Genetics, 2014)

Towards a phylogenetic classification of reef corals: the I ndo‐ P acific genera M erulina , G oniastrea and S capophyllia ( S cleractinia, M erulinidae) - Danwei Huang; Francesca Benzoni; Roberto Arrigoni; Andrew H. Baird; Michael L. Berumen; Jessica Bouwmeester; Loke Ming Chou; Hironobu Fukami; Wilfredo Y. Licuanan; Edward R. Lovell; Rudolf Meier; Peter A. Todd; et al. (Zoologica Scripta, 2014)
Recent advances in scleractinian systematics and taxonomy have been achieved through the integration of molecular and morphological data, as well as rigorous analysis using phylogenetic methods. In this study, we continue in our pursuit of a phylogenetic classification by examining the evolutionary relationships between the closely related reef coral genera M erulina , G oniastrea , P araclavarina and S capophyllia (Merulinidae). In particular, we address the extreme polyphyly of F avites and G oniastrea that was discovered a decade ago. We sampled 145 specimens belonging to 16 species from a wide geographic range in the I ndo‐ P acific, focusing especially on type localities, including the Red Sea, western Indian Ocean and central Pacific. Tree reconstructions based on both nuclear and mitochondrial markers reveal a novel lineage composed of three species previously placed in F avites and G oniastrea . Morphological analyses indicate that this clade, P aragoniastrea H uang, B enzoni & B udd, gen. n., has a unique combination of corallite and subcorallite features observable with scanning electron microscopy and thin sections. Molecular and morphological evidence furthermore indicates that the monotypic genus Paraclavarina is nested within Merulina , and the former is therefore synonymised.

Early Diagnosis of Orthopedic Implant Failure Using Macromolecular Imaging Agents - Ke Ren; Anand Dusad; Yijia Zhang; P. Edward Purdue; Edward V. Fehringer; Kevin L. Garvin; Steven R. Goldring; Dong Wang (Pharmaceutical Research, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The land-ice contribution to 21st-century dynamic sea level rise - T. Howard; J. Ridley; A. K. Pardaens; R. T. W. L. Hurkmans; A. J. Payne; R. H. Giesen; J. A. Lowe; J. L. Bamber; T. L. Edwards; J. Oerlemans (Ocean Science, 2014)
Climate change has the potential to influence global mean sea level through a number of processes including (but not limited to) thermal expansion of the oceans and enhanced land ice melt. In addition to their contribution to global mean sea level change, these two processes (among others) lead to local departures from the global mean sea level change, through a number of mechanisms including the effect on spatial variations in the change of water density and transport, usually termed dynamic sea level changes. In this study, we focus on the component of dynamic sea level change that might be given by additional freshwater inflow to the ocean under scenarios of 21st-century land-based ice melt. We present regional patterns of dynamic sea level change given by a global-coupled atmosphere–ocean climate model forced by spatially and temporally varying projected ice-melt fluxes from three sources: the Antarctic ice sheet, the Greenland Ice Sheet and small glaciers and ice caps. The largest ice melt flux we consider is equivalent to almost 0.7 m of global mean sea level rise over the 21st century. The temporal evolution of the dynamic sea level changes, in the presence of considerable variations in the ice melt flux, is also analysed. We find that the dynamic sea level change associated with the ice melt is small, with the largest changes occurring in the North Atlantic amounting to 3 cm above the global mean rise. Furthermore, the dynamic sea level change associated with the ice melt is similar regardless of whether the simulated ice fluxes are applied to a simulation with fixed CO2 or under a business-as-usual greenhouse gas warming scenario of increasing CO2.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Potential role of winter rainfall in explaining increased moisture in the Mediterranean and Middle East during periods of maximum orbitally-forced insolation seasonality - J. E. Kutzbach; G. Chen; H. Cheng; R. L. Edwards; Z. Liu (Climate Dynamics, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Variants in BET1L and TNRC6B associate with increasing fibroid volume and fibroid type among European Americans - Todd L. Edwards; Katherine E. Hartmann; Digna R. Velez Edwards (Human Genetics, 2013)

Network structure and prevalence of Cryptosporidium in Belding’s ground squirrels - Kimberly L. VanderWaal; Edward R. Atwill; Stacie Hooper; Kelly Buckle; Brenda McCowan (Behavioral Ecology and Sociobiology, 2013)

Parkinson disease loci in the mid-western Amish - M. F. Davis; A. C. Cummings; L. N. D’Aoust; L. Jiang; D. R. Velez Edwards; R. Laux; L. Reinhart-Mercer; D. Fuzzell; W. K. Scott; M. A. Pericak-Vance; S. L. Lee; J. L. Haines (Human Genetics, 2013)

Erratum to: Phreatophytes under stress: transpiration and stomatal conductance of saltcedar (Tamarix spp.) in a high-salinity environment - Edward P. Glenn; Pamela L. Nagler; Kiyomi Morino; Kevin R. Hultine (Plant and Soil, 2013)

Phreatophytes under stress: transpiration and stomatal conductance of saltcedar (Tamarix spp.) in a high-salinity environment - Edward P. Glenn; Pamela L. Nagler; Kiyomi Morino; Kevin R. Hultine (Plant and Soil, 2013)

Nuclear double-fluorescent reporter for in vivo and ex vivo analyses of biological transitions in mouse nuclei - Justin R. Prigge; James A. Wiley; Emily A. Talago; Elise M. Young; Laura L. Johns; Jean A. Kundert; Katherine M. Sonsteng; William P. Halford; Mario R. Capecchi; Edward E. Schmidt (Mammalian Genome, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Estimating traveler populations at airport and cruise terminals for population distribution and dynamics - Warren C. Jochem; Kelly Sims; Edward A. Bright; Marie L. Urban; Amy N. Rose; Phillip R. Coleman; Budhendra L. Bhaduri (Natural Hazards, 2013)

BET1L and TNRC6B associate with uterine fibroid risk among European Americans - Todd L. Edwards; Kara A. Michels; Katherine E. Hartmann; Digna R. Velez Edwards (Human Genetics, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Dispersal limitation, speciation, environmental filtering and niche differentiation influence forest tree communities in West Polynesia - Janet Franklin; Gunnar Keppel; Edward L. Webb; Joshua O. Seamon; Sergio J. Rey; David W. Steadman; Susan K. Wiser; Donald R. Drake (Journal of Biogeography, 2013)
Aim Regional patterns of forest composition in West Polynesia were analysed to determine the relative importance of dispersal limitation, speciation, environmental filtering and biotic interactions. Location West Polynesia (Fiji, Tonga, Samoa). Methods We applied clustering and indicator species analysis to presence/absence data for 397 tree taxa in 338 forest plots to detect groups of plots sharing similar species composition. Patterns of plot composition and co‐occurrence of congeneric species were compared between archipelagos for evidence of dispersal limitation, speciation, and environmental filtering versus competitive displacement or niche differentiation across the three archipelagos at the local (plot) and regional scales. Results Dispersal limitation was evident in the compositional segregation of inland rain forests across the three archipelagos, whereas compositional overlap was widespread for coastal forests, which are composed of species dispersed by water. Within genera, species numbers attenuated from Fiji to Tonga to Samoa, but speciation also contributed to compositional differences in all three island groups. Environmental filtering was suggested by the distinct composition of both secondary and mature inland rain forest versus coastal forest. At the local scale, however, clumping of congeners, which might suggest fine‐scale environmental filtering, was observed for only a minority of inland forest genera. Most genera showed either overdispersion, suggesting competitive displacement or niche differentiation, or patterns not significantly different from random. Main conclusions Well‐established biogeographical patterns of dispersal limitation and speciation contribute to West Polynesian tree diversity at the community scale. Environmental filtering and competitive displacement further structure forest communities; the evidence from this study suggests that environmental filtering is more important at a landscape scale, while competitive displacement may be more important at a local scale, although their relative importance varies considerably among taxa.

Soil warming increases plant species richness but decreases germination from the alpine soil seed bank - Gemma L. Hoyle; Susanna E. Venn; Kathryn J. Steadman; Roger B. Good; Edward J. McAuliffe; Emlyn R. Williams; Adrienne B. Nicotra (Global Change Biology, 2013)
Global warming is occurring more rapidly above the treeline than at lower elevations and alpine areas are predicted to experience above average warming in the future. Temperature is a primary factor in stimulating seed germination and regulating changes in seed dormancy status. Thus, plant regeneration from seed will be crucial to the persistence, migration and post disturbance recruitment of alpine plants in future climates. Here, we present the first assessment of the impact of soil warming on germination from the persistent alpine soil seed bank. Contrary to expectations, soil warming lead to reduced overall germination from the soil seed bank. However, germination response to soil temperature was species specific such that total species richness actually increased by nine with soil warming. We further explored the system by assessing the prevalence of seed dormancy and germination response to soil disturbance, the frequency of which is predicted to increase under climate change. Seeds of a significant proportion of species demonstrated physiological dormancy mechanisms and germination of several species appeared to be intrinsically linked to soil disturbance. In addition, we found no evidence of subalpine species and little evidence of exotic weed species in the soil, suggesting that the soil seed bank will not facilitate their invasion of the alpine zone. In conclusion, changes in recruitment via the alpine soil seed bank can be expected under climate change, as a result of altered dormancy alleviation and germination cues. Furthermore, the alpine soil seed bank, and the species richness therein, has the potential to help maintain local species diversity, support species range shift and moderate species dominance. Implications for alpine management and areas for further study are also discussed.

Gene-environment interactions and obesity traits among postmenopausal African-American and Hispanic women in the Women’s Health Initiative SHARe Study - Digna R. Velez Edwards; Adam C. Naj; Keri Monda; Kari E. North; Marian Neuhouser; Oyunbileg Magvanjav; Ibukun Kusimo; Mara Z. Vitolins; JoAnn E. Manson; Mary Jo O’Sullivan; Evadnie Rampersaud; Todd L. Edwards (Human Genetics, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Building the niche through time: using 13,000 years of data to predict the effects of climate change on three tree species in Europe - L. Maiorano; R. Cheddadi; N. E. Zimmermann; L. Pellissier; B. Petitpierre; J. Pottier; H. Laborde; B. I. Hurdu; P. B. Pearman; A. Psomas; J. S. Singarayer; O. Broennimann; et al. (Global Ecology and Biogeography, 2013)
Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13,000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies , Abies alba and Fagus sylvatica and six climatic variables for the period 13,000 to 1000 yr bp . To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Application of large-scale sequencing to marker discovery in plants - Robert J Henry; Mark Edwards; Daniel L E Waters; Gopala Krishnan S; Peter Bundock; Timothy R Sexton; Ardashir K Masouleh; Catherine J Nock; Julie Pattemore (Journal of Biosciences, 2012)

Egg Placement by Anopheles gambiae (Diptera:Culicidae) as Influenced by Resting Surface Slope and Enclosure - Megan L. Fritz; Edward D. Walker; James R. Miller (Journal of Insect Behavior, 2012)

Seasonal variation in expression of markers in the vitamin D pathway in prostate tissue - Mara M. Epstein; Ove Andrén; Julie L. Kasperzyk; Irene M. Shui; Kathryn L. Penney; Katja Fall; Jennifer R. Rider; Meir J. Stampfer; Swen-Olof Andersson; Edward Giovannucci; Lorelei A. Mucci (Cancer Causes & Control, 2012)

Incorporating climate change into systematic conservation planning - Craig R. Groves; Edward T. Game; Mark G. Anderson; Molly Cross; Carolyn Enquist; Zach Ferdaña; Evan Girvetz; Anne Gondor; Kimberly R. Hall; Jonathan Higgins; Rob Marshall; Ken Popper; et al. (Biodiversity and Conservation, 2012)

Russian wheat aphids ( Diuraphis noxia ) in China: native range expansion or recent introduction? - B. ZHANG; O. R. EDWARDS; L. KANG; S. J. FULLER (Molecular Ecology, 2012)
In this study, we explore the population genetics of the Russian wheat aphid (RWA) ( Diuraphis noxia ), one of the world’s most invasive agricultural pests, in north‐western China. We have analysed the data of 10 microsatellite loci and mitochondrial sequences from 27 populations sampled over 2 years in China. The results confirm that the RWAs are holocyclic in China with high genetic diversity indicating widespread sexual reproduction. Distinct differences in microsatellite genetic diversity and distribution revealed clear geographic isolation between RWA populations in northern and southern Xinjiang, China, with gene flow interrupted across extensive desert regions. Despite frequent grain transportation from north to south in this region, little evidence for RWA translocation as a result of human agricultural activities was found. Consequently, frequent gene flow among northern populations most likely resulted from natural dispersal, potentially facilitated by wind currents. We also found evidence for the long‐term existence and expansion of RWAs in China, despite local opinion that it is an exotic species only present in China since 1975. Our estimated date of RWA expansion throughout China coincides with the debut of wheat domestication and cultivation practices in western Asia in the Holocene. We conclude that western China represents the limit of the far eastern native range of this species. This study is the most comprehensive molecular genetic investigation of the RWA in its native range undertaken to date and provides valuable insights into the history of the association of this aphid with domesticated cereals and wild grasses.

Identification of 104 rapidly-evolving nuclear protein-coding markers for amplification across scaled reptiles using genomic resources - Daniel M. Portik; Perry L. Wood; Jesse L. Grismer; Edward L. Stanley; Todd R. Jackman (Conservation Genetics Resources, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genetic diversity and colony breeding structure in native and introduced ranges of the Formosan subterranean termite, Coptotermes formosanus - Claudia Husseneder; Dawn M. Simms; Jennifer R. Delatte; Changlu Wang; J. Kenneth Grace; Edward L. Vargo (Biological Invasions, 2012)

Evaluation of Fluorescent Phosphatidylserine Substrates for the Aminophospholipid Flippase in Mammalian Cells - Bryan A. Smith; Edward J. O’Neil; Andrew J. Lampkins; James R. Johnson; Jung-Jae Lee; Erin L. Cole; Bradley D. Smith (Journal of Fluorescence, 2012)

MHC region and risk of systemic lupus erythematosus in African American women - Edward A. Ruiz-Narvaez; Patricia A. Fraser; Julie R. Palmer; L. Adrienne Cupples; David Reich; Ying A. Wang; John D. Rioux; Lynn Rosenberg (Human Genetics, 2011)

Influence of insects and fungal pathogens on individual and population parameters of Cirsium arvense in its native and introduced ranges - Michael G. Cripps; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler; Grant R. Edwards (Biological Invasions, 2011)

Patterns of Root Dynamics in Mangrove Forests Along Environmental Gradients in the Florida Coastal Everglades, USA - Edward Castañeda-Moya; Robert R. Twilley; Victor H. Rivera-Monroy; Brian D. Marx; Carlos Coronado-Molina; Sharon M. L. Ewe (Ecosystems, 2011)

Forced and unforced variability of twentieth century North American droughts and pluvials - Benjamin I. Cook; Edward R. Cook; Kevin J. Anchukaitis; Richard Seager; Ron L. Miller (Climate Dynamics, 2011)

Influence of ley duration on the yield and quality of the subsequent cereal crop (spring oats) in an organically managed long-term crop rotation experiment - C. A. Watson; J. A. Baddeley; A. C. Edwards; R. M. Rees; R. L. Walker; C. F. E. Topp (Organic Agriculture, 2011)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

The present and future role of coastal wetland vegetation in protecting shorelines: answering recent challenges to the paradigm - Keryn B. Gedan; Matthew L. Kirwan; Eric Wolanski; Edward B. Barbier; Brian R. Silliman (Climatic Change, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Vegetation Index Methods for Estimating Evapotranspiration by Remote Sensing - Edward P. Glenn; Pamela L. Nagler; Alfredo R. Huete (Surveys in Geophysics, 2010)

Erratum to: Development and Pilot Evaluation of a Cancer-Focused Summer Research Education Program for Navajo Undergraduate Students - Edward R. Garrison; Mark C. Bauer; Brenda L. Hosley; Christi A. Patten; Christine A. Hughes; Mary A. Trapp; Wesley O. Petersen; Martha A. Austin-Garrison; Clarissa N. Bowman; Robert A. Vierkant (Journal of Cancer Education, 2010)

Development and Pilot Evaluation of a Cancer-Focused Summer Research Education Program Navajo Undergraduate Students - Edward R. Garrison; Mark C. Bauer; Brenda L. Hosley; Christi A. Patten; Christine A. Hughes; Mary A. Trapp; Wesley O. Petersen; Martha A. Austin-Garrison; Clarissa N. Bowman; Robert A. Vierkant (Journal of Cancer Education, 2010)

Slowed decomposition is biotically mediated in an ectomycorrhizal, tropical rain forest - Krista L. McGuire; Donald R. Zak; Ivan P. Edwards; Christopher B. Blackwood; Rima Upchurch (Oecologia, 2010)

Intakes of vitamins A, C, and E and use of multiple vitamin supplements and risk of colon cancer: a pooled analysis of prospective cohort studies - Yikyung Park; Donna Spiegelman; David J. Hunter; Demetrius Albanes; Leif Bergkvist; Julie E. Buring; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Lisa Harnack; Ikuko Kato; Vittorio Krogh; et al. (Cancer Causes & Control, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Detection of Food Intake from Swallowing Sequences by Supervised and Unsupervised Methods - Paulo Lopez-Meyer; Oleksandr Makeyev; Stephanie Schuckers; Edward L. Melanson; Michael R. Neuman; Edward Sazonov (Annals of Biomedical Engineering, 2010)

Enemy release does not increase performance of Cirsium arvense in New Zealand - Michael G. Cripps; Grant R. Edwards; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler (Plant Ecology, 2010)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

Local people value environmental services provided by forested parks - Navjot S. Sodhi; Tien Ming Lee; Cagan H. Sekercioglu; Edward L. Webb; Dewi M. Prawiradilaga; David J. Lohman; Naomi E. Pierce; Arvin C. Diesmos; Madhu Rao; Paul R. Ehrlich (Biodiversity and Conservation, 2010)

A unique isolate of beak and feather disease virus isolated from budgerigars (Melopsittacus undulatus) in South Africa - Arvind Varsani; Gillian K. de Villiers; Guy L. Regnard; Robert R. Bragg; Kulsum Kondiah; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2010)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Avian host community structure and prevalence of West Nile virus in Chicago, Illinois - Scott R. Loss; Gabriel L. Hamer; Edward D. Walker; Marilyn O. Ruiz; Tony L. Goldberg; Uriel D. Kitron; Jeffrey D. Brawn (Oecologia, 2009)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Liver lesions in demersal fishes near a large ocean outfall on the San Pedro Shelf, California - Edward Basmadjian; Edwin M. Perkins; Charles R. Phillips; Daniel J. Heilprin; Susan D. Watts; Douglas R. Diener; Mark S. Myers; Kelly A. Koerner; Michael J. Mengel; George Robertson; Jeffrey L. Armstrong; Andrew L. Lissner; et al. (Environmental Monitoring and Assessment, 2008)

Overview of the California climate change scenarios project - Daniel R. Cayan; Amy L. Luers; Guido Franco; Michael Hanemann; Bart Croes; Edward Vine (Climatic Change, 2008)

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Evidence for adiabatic decompression melting in the Southern Mariana Arc from high-Mg lavas and melt inclusions - Edward J. Kohut; Robert J. Stern; Adam J. R. Kent; Roger L. Nielsen; Sherman H. Bloomer; Matthew Leybourne (Contributions to Mineralogy and Petrology, 2006)

Pharmacodynamics of Antiretroviral Agents in HIV-1 Infected Patients: Using Viral Dynamic Models that Incorporate Drug Susceptibility and Adherence - Hulin Wu; Yangxin Huang; Edward P. Acosta; Jeong -Gun Park; Song Yu; Susan L. Rosenkranz; Daniel R. Kuritzkes; Joseph J. Eron; Alan S. Perelson; John G. Gerber (Journal of Pharmacokinetics and Pharmacodynamics, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and the Understorey Environment - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Coupling climate and economic models in a cost-benefit framework: A convex optimisation approach - L. Drouet; N. R. Edwards; A. Haurie (Environmental Modeling & Assessment, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and Introduced Pasture Mixtures - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

(−)-Menthol biosynthesis and molecular genetics - Rodney B. Croteau; Edward M. Davis; Kerry L. Ringer; Mark R. Wildung (The Science of Nature, 2005)

Regeneration of Native Trees in the Presence of Invasive Saltcedar in the Colorado River Delta, Mexico - PAMELA L. NAGLER; OSVEL HINOJOSA‐HUERTA; EDWARD P. GLENN; JAQUELINE GARCIA‐HERNANDEZ; REGGIE ROMO; CHARLES CURTIS; ALFREDO R. HUETE; STEPHEN G. NELSON (Conservation Biology, 2005)
Many riparian zones in the Sonoran Desert have been altered by elimination of the normal flood regime; such changes to the flow regime have contributed to the spread of saltcedar (Tamarix ramosissma Ledeb.), an exotic, salt‐tolerant shrub. It has been proposed that reestablishment of a natural flow regime on these rivers might permit passive restoration of native trees, without the need for aggressive saltcedar clearing programs. We tested this proposition in the Colorado River delta in Mexico, which has received a series of large‐volume water releases from U.S. dams over the past 20 years. We mapped the vegetation of the delta riparian corridor through ground and aerial surveys (1999–2002) and satellite imagery (1992–2002) and related vegetation changes to river flood flows and fire events. Although saltcedar is still the dominant plant in the delta, native cottonwood ( Populus fremontii S. Wats.) and willow (Salix gooddingii C. Ball) trees have regenerated multiple times because of frequent flood releases from U.S. dams since 1981. Tree populations are young and dynamic (ages 5–10 years). The primary cause of tree mortality between floods is fire. Biomass in the floodplain, as measured by the normalized difference vegetation index on satellite images, responds positively even to low‐volume (but long‐duration) flood events. Our results support the hypothesis that restoration of a pulse flood regime will regenerate native riparian vegetation despite the presence of a dominant invasive species, but fire management will be necessary to allow mature tree stands to develop.

Hydroxyl and Peroxy Radical Chemistry in a Rural Area of Central Pennsylvania: Observations and Model Comparisons - Xinrong Ren; William H. Brune; Christopher A. Cantrell; Gavin D. Edwards; Terry Shirley; Andrew R. Metcalf; Robert L. Lesher (Journal of Atmospheric Chemistry, 2005)

Alteration of the embryo transcriptome of hexaploid winter wheat (Triticum aestivum cv. Mercia) during maturation and germination - Ian D. Wilson; Gary L. A. Barker; Chungui Lu; Jane A. Coghill; Richard W. Beswick; John R. Lenton; Keith J. Edwards (Functional & Integrative Genomics, 2005)

A general biophysical model of larval cod ( Gadus morhua ) growth applied to populations on Georges Bank - R. G. LOUGH; L. J. BUCKLEY; F. E. WERNER; J. A. QUINLAN; K. PEHRSON EDWARDS (Fisheries Oceanography, 2005)
Field‐derived growth rates (RNA‐DNA based) of cod ( Gadus morhua ) larvae collected on the southern flank of Georges Bank were higher on average in May 1993 than May 1994, despite the apparent higher abundance of potential prey in 1994. A biophysical modeling study is presented here in which factors are examined that may have led to the difference in population mean growth. A one‐dimensional physical model, forced by winds and tides, was used to simulate the vertical structure (of currents, temperature field, and turbulent kinetic energy dissipation rate) following a column of water in a Lagrangian sense at a site on the southern flank of Georges Bank over 5‐day periods in late May of 1993 and 1994. The biophysical model and observed zooplankton abundance allowed us to explore the vertical structure and temporal (hourly) evolution of feeding and growth for cod larvae in relation to environmental conditions. Our trophodynamic model is improved over previous versions and now includes the effect of light on larval feeding response, as well as the effect of temperature on larval metabolic costs, ingestion, and digestion. Larval prey profiles, comprising four copepod species, were used from a time series of 1/4‐m 2 MOCNESS tows to define the prey field. Data from a collateral time‐series of larval gut contents (1‐m 2 MOCNESS tows) was used to define maximum ingestion (satiation level) and prey selection. Model outputs provide depth‐dependent estimates of growth, prey biomass ingested, larval length, and larval weight. Water‐column growth‐rate profiles were made for four size classes of larvae (5, 6, 7 and 9 mm) under the environmental conditions observed in May 1993 and 1994. A weighted‐mean growth rate based on the mean vertical distribution of larvae was estimated for each size class. In all cases, when using all available potential prey, the model‐derived 1994 growth rates were higher (by 3–6% day −1 ) than those for 1993. However, simulations in which 7‐mm larvae followed the field‐derived weighted mean depth over the sampling period, and were limited to their preferred Pseudocalanus prey, resulted in average growth of 12.2% day −1 for 1993 and 9.7% day −1 for 1994. These compared closely to the field growth means of 11.3% day −1 in 1993 and 9.8% day −1 in 1994. Thus, the lower observed growth in May 1994 may have resulted from depth‐dependent food limitation and prey‐selectivity coupled with the greater metabolic costs induced by the higher temperature that year.

Structure–activity relationships of dinucleotides: Potent and selective agonists of P2Y receptors - Sammy R. Shaver; Janet L. Rideout; William Pendergast; James G. Douglass; Edward G. Brown; José L. Boyer; Roshni I. Patel; Catherine C. Redick; Arthur C. Jones; Maryse Picher; Benjamin R. Yerxa (Purinergic Signalling, 2005)

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Specific Status of Propithecus spp. - Mireya I. Mayor; Julie A. Sommer; Marlys L. Houck; John R. Zaonarivelo; Patricia C. Wright; Colleen Ingram; Stacia R. Engel; Edward E. Louis (International Journal of Primatology, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

P-glycoprotein Expression, Localization, and Function in Sandwich-Cultured Primary Rat and Human Hepatocytes: Relevance to the Hepatobiliary Disposition of a Model Opioid Peptide - Keith A. Hoffmaster; Ryan Z. Turncliff; Edward L. LeCluyse; Richard B. Kim; Peter J. Meier; Kim L. R. Brouwer (Pharmaceutical Research, 2004)

Characterisation of early transcriptional changes involving multiple signalling pathways in the Mla13 barley interaction with powdery mildew ( Blumeria graminis f. sp. hordei ) - Ingo Hein; Edward I. Campbell; Mary Woodhead; Peter E. Hedley; Vanessa Young; Wayne L. Morris; Luke Ramsay; Joerg Stockhaus; Paul R. J. Birch; Gary D. Lyon; Adrian C. Newton (Planta, 2004)

Electrical stimulation driving functional improvements and cortical changes in subjects with stroke - Teresa J. Kimberley; Scott M. Lewis; Edward J. Auerbach; Lisa L. Dorsey; Jeanne M. Lojovich; James R. Carey (Experimental Brain Research, 2004)

Effects of Land Cover on Stream Ecosystems: Roles of Empirical Models and Scaling Issues - David L. Strayer; R. Edward Beighley; Lisa C. Thompson; Shane Brooks; Christer Nilsson; Gilles Pinay; Robert J. Naiman (Ecosystems, 2003)

Receptor-specific targeting with complementary peptide nucleic acids conjugated to peptide analogs and radionuclides - Eric Wickstrom; Mathew L. Thakur; Edward R. Sauter (International Journal of Peptide Research and Therapeutics, 2003)

Chaetae and mechanical function: tools no Metazoan class should be without - Sarah A. Woodin; Rachel A. Merz; Florence M. Thomas; Deirdre R. Edwards; Irene L. Garcia (Hydrobiologia, 2003)

Incidence of Stress in Benthic Communities along the U.S. Atlantic and Gulf of Mexico Coasts within Different Ranges of Sediment Contamination from Chemical Mixtures - Jeffrey L. Hyland; W. Leonard Balthis; Virginia D. Engle; Edward R. Long; John F. Paul; J. Kevin Summers; Robert F. Van Dolah (Environmental Monitoring and Assessment, 2003)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)

Optimization of culture conditions for determining hepatobiliary disposition of taurocholate in sandwich-cultured rat hepatocytes - Priyamvada Chandra; Edward L. Lecluyse; Kim L. R. Brouwer (In Vitro Cellular & Developmental Biology - Animal, 2001)

OPTIMIZATION OF CULTURE CONDITIONS FOR DETERMINING HEPATOBILIARY DISPOSITION OF TAUROCHOLATE IN SANDWICH-CULTURED RAT HEPATOCYTES - PRIYAMVADA CHANDRA; EDWARD L. LECLUYSE; KIM L. R. BROUWER (In Vitro Cellular & Developmental Biology - Animal, 2001)

Microsatellites for Barren Brome ( Anisantha sterilis ) - J. M. Green; K. J. Edwards; S. L. Usher; J. H. A. Barker; E. J. P. Marshall; R. J. Froud‐Williams; A. Karp (Molecular Ecology, 2000)

Phylogeny of Marine Bacillus Isolates from the Gulf of Mexico - Janet L. Siefert; Maia Larios-Sanz; Lawrence K. Nakamura; Ralph A. Slepecky; John H. Paul; Edward R. B. Moore; George E. Fox; Peter Jurtshuk, Jr. (Current Microbiology, 2000)

Comparative toxicity of trivalent and pentavalent inorganic and methylated arsenicals in rat and human cells - Miroslav Styblo; Luz M. Del Razo; Libia Vega; Dori R. Germolec; Edward L. LeCluyse; Geraldine A. Hamilton; William Reed; Changqing Wang; William R. Cullen; David J. Thomas (Archives of Toxicology, 2000)

Characterisation and analysis of microsatellite loci in a mangrove species, Avicennia marina (Forsk.) Vierh. (Avicenniaceae) - T. L. Maguire; K. J. Edwards; P. Saenger; R. Henry (Theoretical and Applied Genetics, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

A General Method for Constrained Analysis of Fluorescence Anisotropy Decay: Application of the Steady-State Anisotropy - Edward L. Rachofsky; Barnabas Wolf; Carl N. Bialik; J. B. Alexander Ross; William R. Laws (Journal of Fluorescence, 1999)

Abundance and polymorphism of microsatellite markers in the tea tree (Melaleuca alternifolia, Myrtaceae) - M. Rossetto; A. McLauchlan; F. C. L. Harriss; R. J. Henry; P. R. Baverstock; L. S. Lee; T. L. Maguire; K. J. Edwards (Theoretical and Applied Genetics, 1999)

Partial Maintenance of Taurocholate Uptake by Adult Rat Hepatocytes Cultured in a Collagen Sandwich Configuration - Xingrong Liu; Kim L. R. Brouwer; Liang-Sheng L. Gan; Kenneth R. Brouwer; Bruno Stieger; Peter J. Meier; Kenneth L. Audus; Edward L. LeCluyse (Pharmaceutical Research, 1998)

Effect of environmental temperature on the interactive developmental toxicity of radiofrequency radiation and 2-methoxyethanol in rats - B. K. Nelson; D. L. Conover; E. F. Krieg Jr; D. L. Snyder; R. M. Edwards (International Archives of Occupational and Environmental Health, 1998)

Numerical analysis of the hydrogeologic controls in a layered coastal aquifer system, Oahu, Hawaii, USA - Delwyn S. Oki; William R. Souza; Edward L. Bolke; Glenn R. Bauer (Hydrogeology Journal, 1998)

Effects of delivery rate and non-contingent infusion of cocaine on cocaine self-administration in rhesus monkeys - L. V. Panlilio; Steven R. Goldberg; Joanne P. Gilman; Rebecca Jufer; Edward J. Cone; Charles W. Schindler (Psychopharmacology, 1998)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

Single-dose dextropropoxyphene in post-operative pain: a quantitative systematic review - S. L. Collins; J. E. Edwards; R. A. Moore; H. J. McQuay (European Journal of Clinical Pharmacology, 1998)

Discrimination of three Typhlodromalus species (Acari: Phytoseiidae) using random amplified polymorphic DNA markers - Owain R. Edwards; E.L. Melo; L. Smith; M.A. Hoy (Experimental and Applied Acarology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Mass spectrometric dating of flowstones from Stump Cross Caverns and Lancaster Hole, Yorkshire: palaeoclimate implications - ANDY BAKER; PETER L. SMART; R. LAWRENCE EDWARDS (Journal of Quaternary Science, 1996)

Mass spectrometric dating of flowstones from Stump Cross Caverns and Lancaster Hole, Yorkshire: palaeoclimate implications - ANDY BAKER; PETER L. SMART; R. LAWRENCE EDWARDS (Journal of Quaternary Science, 1996)

Uptake of polychlorobiphenyl congeners by purple loosestrife (Lythrum salicaria) on the banks of the Hudson river - Brian Bush; Lana A. Shane; Lloyd R. Wilson; Edward L. Barnard; Dawn Barnes (Archives of Environmental Contamination and Toxicology, 1986)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)